Laminate and display device
By using a laminated body of a specific structure in an organic EL display device, including a first phase element, a vertical polarizing film, a polarizing plate and a second phase element that displays phase difference in the plane, the unevenness of observation in the inclined direction through the polarized sunglasses during white display is solved, and a more uniform display effect is achieved.
Patent Information
- Application Number
- CN202411342835.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-23
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-28
AI Technical Summary
When the organic EL display device is viewed from the inclined direction through the polarized sunglasses during white display, unevenness occurs.
A laminated body is adopted, which sequentially includes a first phase element, a vertical polarizing film, a polarizing plate and a second phase element that displays phase differences in the plane. The vertical polarizing film consists of polymeric liquid crystal compounds and dichroic pigments, which meet specific absorbance conditions to suppress display unevenness.
The unevenness of the white display is effectively suppressed from the inclined direction through the polarized sunglasses, and the observationality of the organic EL display device is improved.
Smart Images

Figure CN119717107A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and a display device. Background Art
[0002] Image display devices such as organic EL display devices are widely used in mobile phones, smart phones, notebook computers, information terminals, etc. Attempts have been made to enable such image display devices to exert functions according to their applications and usage conditions.
[0003] For example, Patent Document 1 discloses a laminated body in which a light absorption anisotropic film (vertical polarizing film), a horizontally aligned phase difference film i (first phase element), a polarizer, and a horizontally aligned phase difference film ii (second phase element) are sequentially laminated. An organic EL display device using the laminated body can suppress internal reflection of the organic EL display device when viewed from the front by adjusting the in-plane phase difference and slow axis direction of the horizontally aligned phase difference film ii (second phase element), thereby making the viewing performance of the screen excellent.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-176121 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, it is known that unevenness occurs when the image display device including the laminate described in Patent Document 1 is viewed from an oblique direction through polarized sunglasses during white display.
[0009] Therefore, an object of the present invention is to provide a laminated body capable of realizing an organic EL display device in which unevenness in white display is suppressed when the device is viewed from an oblique direction through polarized sunglasses.
[0010] Means for solving problems
[0011] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. That is, the present invention includes the following preferred embodiments.
[0012] [1] A laminate comprising, in order, a first phase element, a vertical polarizing film, a polarizing plate, and a second phase element,
[0013] The first phase element is a phase element that exhibits a phase difference within a plane.
[0014] The angle between the slow axis of the first phase element and the absorption axis of the polarizer is greater than or equal to 35° and less than or equal to 55°, or greater than or equal to 125° and less than or equal to 145°.
[0015] The vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic pigment, and satisfies the following formulas (1) and (2):
[0016] 0.001≤AxC≤0.3 (1)
[0017] AxC(z=60) / AxC>2 (2)
[0018] [In formulas (1) and (2), AxC and AxC(z=60) are the absorbances of the perpendicular polarizing film at the absorption maximum wavelength of 400 to 750 nm.
[0019] AxC represents the absorbance of linear polarized light vibrating in the x-axis direction, and AxC(z=60) represents the absorbance of linear polarized light vibrating in the x-axis direction when the vertical polarizing film is rotated 60° with the y-axis as the rotation axis.
[0020] Here, the x-axis refers to an arbitrary direction in the plane of the perpendicular polarizing film, the y-axis refers to a direction perpendicular to the x-axis in the film plane, and the z-axis refers to a thickness direction of the perpendicular polarizing film].
[0021] [2] The laminate according to [1], wherein the absorption maximum wavelength of the vertical polarizing film in the oblique direction is 500 nm or more and less than 700 nm, and the first phase element satisfies the following formula (3):
[0022] Re(450)≤135nm (3)
[0023] [In formula (3), Re(450) represents the in-plane phase difference value of the first phase element at a wavelength of 450 nm].
[0024] [3] The laminate according to [1], wherein the absorption maximum wavelength of the vertical polarizing film in the oblique direction is greater than or equal to 400 nm and less than 500 nm, and the first phase element satisfies at least one of the following equations (4) and (5):
[0025] Re(550)≥95nm (4)
[0026] Re(650)≥95nm (5)
[0027] [In equations (4) and (5), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm].
[0028] [4] The laminate according to [1], wherein the absorption maximum wavelength of the vertical polarizing film in the oblique direction is greater than or equal to 400 nm and less than 600 nm, and the first phase element satisfies the following formula (6):
[0029] Re(650)≥95nm (6)
[0030] [In formula (6), Re(650) represents the in-plane phase difference value of the first phase element at a wavelength of 650 nm].
[0031] [5] The laminate according to [1], wherein the maximum absorption wavelength of the vertical polarizing film in the oblique direction is 600 to 700 nm, and the first phase element satisfies at least one of the following equations (7) and (8):
[0032] Re(450)≤135nm (7)
[0033] Re(550)≤150nm (8)
[0034] [In equations (7) and (8), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm].
[0035] [6] The laminate according to any one of [1] to [5], wherein the second phase element comprises a cured film of a composition containing a polymerizable liquid crystal compound.
[0036] [7] The laminate according to any one of [1] to [5], wherein the polarizer comprises a cured film of a composition containing a polymerizable liquid crystal compound and a dichroic dye.
[0037] [8] An organic EL display device comprising the laminate according to any one of [1] to [7].
[0038] Effects of the Invention
[0039] According to the present invention, it is possible to provide a laminated body capable of realizing an organic EL display device in which unevenness in white display is suppressed when the device is viewed from an oblique direction through polarized sunglasses. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a schematic cross-sectional view showing an example of the layer structure of the laminate of the present invention.
[0041] Figure 2 This is a schematic cross-sectional view showing an example of the layer structure of the laminate of the present invention.
[0042] Figure 3 This is a diagram showing the x-axis, the Y-axis, and the Z-axis in the perpendicular polarizing film included in the laminate of the present invention. DETAILED DESCRIPTION
[0043] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the gist of the present invention.
[0044] The laminate of the present invention comprises, in order: a first phase element showing a phase difference in a plane, a vertical polarizing film which is a cured product of a composition comprising a polymerizable liquid crystal compound and a dichroic dye, a polarizing plate, and a second phase element. Figure 1 and Figure 2 An example of the layer structure of the laminated body of the present invention will be described, but the laminated body of the present invention is not limited to these embodiments.
[0045] Figure 1 The laminate 21 of the present invention shown in this embodiment includes, in order, a first phase element 1, a vertical polarizing film 2, a polarizing plate 3, and a second phase element 4. The laminate of the present invention is usually assembled in an image display device or the like with the first phase element located on the observation side.
[0046] like Figure 2 As shown, the second phase element 4 may be incorporated as one of the phase elements constituting the multiple phase difference plate 11 . In this case, the multiple phase difference plate 11 includes another phase element 5 different from the second phase element 4 .
[0047] The laminate of the present invention may further include other layers in addition to the first phase element, the vertical polarizing film, the polarizer, and the second phase element, as long as the effect of the present invention is not affected. As other layers, for example, protective layers such as hard coatings and transparent protective films, substrate layers, adhesive layers, etc. can be cited. These other layers are usually non-oriented, optically isotropic layers, and are colorless and transparent.
[0048] The vertical polarizing film is a cured product obtained by curing a polymerizable liquid crystal compound and a dichroic dye in a state where the polymerizable liquid crystal compound and the dichroic dye are oriented in a vertical direction relative to the plane of the obtained cured product, and satisfies the following formulas (1) and (2):
[0049] 0.001≤AxC≤0.3 (1)
[0050] AxC(z=60) / AxC>2 (2)
[0051] [In formulas (1) and (2), AxC and AxC(z=60) are the absorbances of the vertical polarizing film at the absorption maximum wavelength of 400 to 750 nm.
[0052] AxC represents the absorbance of linear polarized light vibrating in the x-axis direction, AxC(z=60) represents the absorbance of linear polarized light vibrating in the x-axis direction when the vertical polarizing film is rotated 60° with the y-axis as the rotation axis, wherein the x-axis refers to any direction within the plane of the vertical polarizing film, the y-axis refers to the direction perpendicular to the x-axis within the film plane, and the z-axis refers to the thickness direction of the vertical polarizing film].
[0053] The above formula (1) means that the absorbance in the front direction of the vertical polarizing film is greater than 0.001 and less than 0.3. The smaller the value of AxC, the more accurately the dichroic pigment is oriented in the vertical direction relative to the plane of the obtained vertical polarizing film. In addition, as shown in formula (2), AxC (z = 60) is sufficiently large relative to AxC. Therefore, if there is light incident on the vertical polarizing film from the oblique direction of the polarizing plate side, the wavelength component of the maximum absorbance AxC (z = 60) in the oblique direction of the vertical polarizing film is absorbed, and the remaining wavelength components are transmitted. The transmitted wavelength component is incident on the first phase element from the oblique direction and is emitted from the first phase element in the oblique direction. The details are not yet clear, but it is believed that the light incident and transmitted in the oblique direction passes through the first phase element that displays a phase difference in the plane, which is one of the reasons why the display unevenness when observing the white display from an oblique direction through sunglasses can be suppressed. It is believed that if the first phase element functions as a λ / 4 plate with respect to the wavelength component incident and transmitted along the oblique direction, the obliquely emitted light is observed closer to circularly polarized light, and the display unevenness when the white display is observed from an oblique direction through sunglasses can be more effectively suppressed, so it is preferred.
[0054] It should be noted that the absorbance in this specification refers to the absorbance when measured in a state where the influence of interface reflection during measurement is completely eliminated. As a method for eliminating the influence of interface reflection, for example, the following method can be cited: using a spectrophotometer, the absorbance at a wavelength where the absorption of the compound can be ignored among long wavelengths such as 800 nm is set to 0, and in this state, the absorbance at the wavelength in the region where the absorption of the compound exists is measured.
[0055] When the value of AxC exceeds 0.3, the screen becomes dark (brightness decreases), so the value of AxC is preferably 0.1 or less, and more preferably 0.05 or less. In addition, the lower limit of the value of AxC is usually 0.001 or more, preferably 0.003 or more, and more preferably 0.005 or more.
[0056] The above-mentioned AxC (z=60) can be measured by incident linear polarized light identical to the linear polarized light for measuring Ax, in a state where the vertical polarizing film is rotated 60° with the y-axis as the rotation axis. Here, the rotation of the film is performed by rotating the film in the state where Ax is measured by 60° with the y-axis as the rotation axis in the incident direction of the linear polarized light. Regarding the above-mentioned value of AxC (z=60) / AxC, if its numerical value is 2 or less, it is difficult to obtain good optical anisotropy, and the observability when observing the organic EL device from an oblique direction through polarized sunglasses during white display deteriorates, so the value of AxC (z=60) / AxC is preferably 3 or more, more preferably 5 or more. On the other hand, if the value of AxC (z=60) / AxC is too large, it is difficult to obtain and produce, so the value of AxC (z=60) / AxC is preferably 50 or less, more preferably 30 or less, further preferably 20 or less, and particularly preferably 15 or less. AxC (z=60) is preferably 0.01 or more, more preferably 0.03 or more, further preferably 0.04 or more, and is preferably 1.0 or less, more preferably 0.5 or less, further preferably 0.3 or less, and particularly preferably 0.2 or less.
[0057] It should be noted that the absorbance of linear polarized light vibrating in the y-axis direction is expressed as AyC. In the vertical polarizing film described in the present invention, AxC and AyC are generally substantially equal. When AxC and AyC are different, there is dichroism in the plane, and in this case, there is a tendency for the front color tone of the vertical polarizing film to be colored more.
[0058] In the present invention, AxC and AxC (Z = 60) in the vertical polarizing film can be controlled by adjusting the film thickness, the conditions of the manufacturing process, the types and the mixing amounts of the polymerizable liquid crystal compound and the dichroic pigment constituting the vertical polarizing film, etc. In addition, usually, the value of AxC (z = 60) / AxC is about 2 to 10 when the polymerizable liquid crystal compound is a nematic liquid crystal, and is about 5 to 30 when it is a smectic liquid crystal, and can be appropriately selected according to the target optical properties.
[0059] In the present invention, the vertical polarizing film is a cured product of a composition comprising a polymerizable liquid crystal compound and a dichroic pigment. The polymerizable liquid crystal compound refers to a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group. The polymerizable liquid crystal compound is not particularly limited as long as it can form a vertical polarizing film satisfying the above formulas (1) and (2). For example, a polymerizable liquid crystal compound known in the art of phase difference films can be used.
[0060] A polymerizable group refers to a group that can participate in a polymerization reaction. A photopolymerizable group refers to a polymerizable group, and a group that can participate in a polymerization reaction through reactive species generated by a photopolymerization initiator, such as active free radicals, acids, etc. As a photopolymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxiranyl, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxiranyl and oxetane are preferred, and acryloyloxy is more preferred. The liquid crystal properties displayed by the polymerizable liquid crystal compound can be thermotropic liquid crystal or lyotropic liquid crystal, but thermotropic liquid crystal is preferred from the perspective of being able to perform dense film thickness control. In addition, as a phase sequence structure in a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. From the viewpoint that the value of AxC becomes smaller and the value of AxC (z = 60) / AxC becomes larger, a smectic liquid crystal is preferred. The polymerizable liquid crystal compound can be used alone or in combination of two or more.
[0061] The dichroic pigment in the present invention refers to a pigment having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. The dichroic pigment is not particularly limited, as long as it has such a property and can form a vertical polarizing film that satisfies the above formulas (1) and (2). The dichroic pigment can be a dye or a pigment, and two or more dyes can be used in combination, and two or more pigments can be used in combination, and a dye and a pigment can be used in combination.
[0062] In the present invention, the first phase element is a phase element that shows a phase difference in the plane. Specifically, for example, it can be a phase difference film that shows a phase difference in the plane formed by stretching a thermoplastic resin film, or a phase difference film that shows a phase difference in the plane composed of a polymer of a polymerizable liquid crystal compound. In the present invention, the phase difference film as the first phase element is composed of a layer of a polymer containing a polymerizable liquid crystal compound alone, or is composed of two layers of the layer and an orientation layer. The in-plane phase difference Re (λ) of the first phase element preferably represents an in-plane phase difference of a wavelength roughly equivalent to 1 / 4 of the wavelength λ in the visible light wavelength region. Such a first phase element can function as a so-called λ / 4 plate.
[0063] In the present invention, the angle between the slow axis of the first phase element and the absorption axis of the polarizer described later is usually 35° to 55° or 125° to 145°, preferably 40° to 50° or 130° to 140°, and ideally 45° or 135°. The first phase element is a λ / 4 plate that displays the above-mentioned in-plane phase difference, and the angle between its slow axis and the absorption axis of the polarizer described later is within the above range, so that the light emitted toward the front from the image display device through the polarizer, the vertical polarizing film and the first phase element can become circularly polarized light. Therefore, the displayed image can be easily observed even through sunglasses from the front. The angle between the slow axis of the first phase element and the absorption axis of the polarizer described later can be adjusted to the above range, for example, by adjusting the bonding angle, making the slow axis of the first phase element or the absorption axis of the polarizer consistent with the specified angle in advance, and bonding in a roll-to-roll manner.
[0064] In a preferred embodiment of the present invention, the first phase element preferably functions as a λ / 4 plate for the wavelength component of the vertical polarizing film. Specifically, for example, when the maximum absorption wavelength in the tilt direction of the vertical polarizing film is 500nm to 700nm, light with a wavelength less than 500nm, such as 450nm, is more easily transmitted. Therefore, the first phase element preferably satisfies the following formula (3):
[0065] Re(450)≤135nm (3)
[0066] [In formula (3), Re(450) represents the in-plane phase difference value of the first phase element at a wavelength of 450 nm].
[0067] The Re(450) of the first phase element is more preferably 125 nm or less, further preferably 125 nm or less, further preferably 120 nm or less, and particularly preferably 110 nm or less.
[0068] Furthermore, Re(450) is usually 85 nm or more, preferably 90 nm or more, and more preferably 95 nm or more.
[0069] In the present invention, the absorption maximum wavelength in the oblique direction of the vertical polarizing film can be adjusted to a desired range by, for example, appropriately adjusting the type, combination, and ratio of the dichroic pigments contained in the vertical polarizing film. In addition, the absorption maximum wavelength in the oblique direction of the vertical polarizing film can be measured, for example, using a spectrophotometer. Specifically, the measurement can be performed, for example, according to the method described in the embodiments described below.
[0070] The in-plane phase difference Re(λ) of the first phase element can be calculated according to the following formula:
[0071] Re(λ)=(nx(λ)-ny(λ))×d
[0072] [wherein nx(λ) represents the principal refractive index at a wavelength λnm in the plane of the first phase element, ny(λ) represents the refractive index at a wavelength λnm in a direction orthogonal to the direction of nx in the same plane as nx, and d represents the film thickness of the first phase element].
[0073] Therefore, in order to obtain the desired in-plane phase difference value, it is sufficient to adjust the three-dimensional refractive index and the film thickness d. Specifically, for example, the thickness of the first phase element; the type and / or amount of the additive contained in the first phase element; the manufacturing conditions of the first phase element, etc. can be appropriately adjusted to adjust to the desired range. In addition, the in-plane phase difference value can be measured using a phase difference measuring device, for example.
[0074] In a preferred embodiment of the laminate of the present invention, for example, when the absorption maximum wavelength in the oblique direction of the vertical polarizing film is 400 nm or more and less than 500 nm, light with a wavelength exceeding 500 nm is relatively easy to transmit. Therefore, the first phase element preferably satisfies at least one of the following equations (4) and (5), and more preferably satisfies both of the following equations (4) and (5):
[0075] Re(550)≥95nm (4)
[0076] Re(650)≥95nm (5)
[0077] [In equations (4) and (5), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm].
[0078] The Re(550) of the first phase element is preferably greater than 120 nm, more preferably greater than 130 nm, further preferably greater than 135 nm, and particularly preferably greater than 140 nm. In addition, Re(650) is preferably greater than 120 nm, more preferably greater than 130 nm, and further preferably greater than 135 nm. In addition, Re(550) is usually less than 180 nm, preferably less than 165 nm, and further preferably less than 150 nm, and Re(650) is usually less than 200 nm, preferably less than 180 nm, and further preferably less than 160 nm. It should be noted that from the viewpoint of suppressing the coloring of internal reflected light during black display, the first phase element more preferably satisfies both of the above equations (4) and (5).
[0079] In another preferred embodiment of the laminate of the present invention, for example, when the absorption maximum wavelength in the oblique direction of the vertical polarizing film is greater than or equal to 400 nm and less than 600 nm, light with a wavelength exceeding 600 nm is relatively easy to transmit. Therefore, the first phase element preferably satisfies the following formula (6):
[0080] Re(650)≥95nm (6)
[0081] [In formula (6), Re(650) represents the in-plane phase difference value of the first phase element at a wavelength of 650 nm].
[0082] Re(650) is preferably 110 nm or more, more preferably 120 nm or more, further preferably 130 nm or more, and particularly preferably 140 nm or more. Re(650) is usually 200 nm or less, preferably 180 nm or less, and further preferably 160 nm or less.
[0083] In a preferred embodiment of the laminate of the present invention, for example, when the absorption maximum wavelength in the oblique direction of the vertical polarizing film is 600 to 700 nm, light with a wavelength less than 600 nm is relatively easy to transmit. Therefore, the first phase element preferably satisfies at least one of the following equations (7) and (8), and more preferably satisfies both of the following equations (7) and (8):
[0084] Re(450)≤135nm (7)
[0085] Re(550)≤150nm (8)
[0086] [In equations (7) and (8), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm].
[0087] Re(450) is preferably 130 nm or less, more preferably 125 nm or less, further preferably 115 nm or less, and particularly preferably 115 nm or less. In addition, Re(550) is preferably 140 nm or less, more preferably 130 nm or less, further preferably 120 nm or less, and further preferably 110 nm or less. Re(450) is usually 80 nm or more, preferably 85 nm or more, and further preferably 90 nm or more, and Re(550) is usually 80 nm or more, preferably 90 nm or more, and further preferably 95 nm or more.
[0088] In a preferred embodiment of the laminate of the present invention, the second phase element or the multiple phase difference plate can be a so-called λ / 4 plate, and the in-plane phase difference measured from the front can be approximately one-quarter (approximately λ / 4) of the wavelength λ in the visible light range. In addition, in a preferred embodiment, the slow axis of the second phase element or the multiple phase difference plate can usually be approximately 45° relative to the absorption axis of the polarizer.
[0089] In the case where the second phase element or the multiple phase difference plate is a so-called λ / 4 plate, the polarizer and the second phase element or the multiple phase difference plate constituting the laminate of the present invention can function as a circular polarizer for light incident from the front side of the polarizer. In contrast, the phase difference value of the second phase element for light incident from the oblique direction of the polarizer side deviates from the actual in-plane phase difference value of the second phase element. Similarly, the angle between the slow axis of the second phase element and the absorption axis of the polarizer deviates by 45°.
[0090] Therefore, the polarizer and the second phase element or the multiple phase difference plate do not function as circular polarizers for light incident from an oblique direction, but can function as elliptical polarizers. In this case, when the organic EL display device is observed from an oblique direction during black display, sometimes a small amount of light reflected inside the display device appears to be colored. In the laminate of the present invention, since the vertical polarizing film containing a pigment capable of absorbing light reflected inside the display device is located between the polarizer and the first phase element, in addition to suppressing the unevenness seen when the organic EL display device is observed from an oblique direction through polarized sunglasses during white display, coloring during black display can also be suppressed.
[0091] Hereinafter, each layer constituting the laminate of the present invention will be described in detail.
[0092] <Vertical Polarizing Film>
[0093] In the present invention, the vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye.
[0094] The polymerizable liquid crystal compound forming the vertical polarizing film in the present invention may be a nematic liquid crystal or a smectic liquid crystal, and is preferably a smectic liquid crystal from the viewpoint of absorption selectivity.
[0095] As a polymerizable liquid crystal compound forming the vertical polarizing film in the present invention, in the case of using a polymerizable liquid crystal compound showing smectic liquid crystal properties, from the viewpoint of being able to achieve a higher degree of orientation order, the polymerizable liquid crystal compound is more preferably a high-order smectic phase (high-order smectic liquid crystal state). Here, the high-order smectic phase refers to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase and smectic L phase, among which smectic B phase, smectic F phase and smectic I phase are more preferred. Liquid crystal properties can be thermotropic liquid crystals or lyotropic liquid crystals. From the aspect of being able to perform dense film thickness control, thermotropic liquid crystals are preferred. In addition, the polymerizable liquid crystal compound showing smectic liquid crystal properties can be a monomer, an oligomer formed by polymerization of polymerizable groups, or a polymer.
[0096] The polymerizable liquid crystal compound showing smectic liquid crystal properties is a liquid crystal compound having at least one polymerizable group. From the viewpoint of improving the heat resistance of the vertical polarizing film, a liquid crystal compound having two or more polymerizable groups is preferred. As the polymerizable group, for example, (meth)acryloyloxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, oxirane, oxetane, etc. can be cited. Among them, from the perspective of easy manufacture, easy improvement of the heat resistance of the vertical polarizing film, and easy adjustment of the adhesion between the vertical polarizing film and the substrate, it is preferred to contain (meth)acryloyloxy.
[0097] Examples of polymerizable liquid crystal compounds that exhibit smectic liquid crystal properties include compounds represented by the following formula (Z) (hereinafter, sometimes referred to as “polymerizable liquid crystal compounds (Z)”).
[0098] [Chemical formula 1]
[0099] U 1z -V 1z -W 1z -(X 1z -Y 1z -) nz -X 2z -W 2z -V 2z -U 2z (Z)
[0100] [In formula (Z), X 1z and X 2z Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.1z and X 2z At least one of them is 1,4-phenylene which may have a substituent or cyclohexane-1,4-diyl which may have a substituent.
[0101] Y 1z It is a single bond or a divalent linking group.
[0102] nz is 1 to 3. When nz is 2 or more, multiple x 1z They can be the same or different. 2z Can be used with multiple X 1z In addition, when nz is 2 or more, multiple Y 1z They may be the same as or different from each other. From the viewpoint of liquid crystallinity, nz is preferably 2 or more.
[0103] U 1z represents a hydrogen atom or a (meth)acryloyloxy group.
[0104] U 2z It represents a polymerizable group.
[0105] W 1z and W 2z Each is independently a single bond or a divalent linking group.
[0106] V 1z and V 2z Each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, wherein -CH2- constituting the alkanediyl group may be replaced by -O-, -CO-, -S- or -NH-.]
[0107] In the polymerizable liquid crystal compound (Z), X 1z and X 2z Each of them is independently preferably 1,4-phenylene which may have a substituent, or cyclohexane-1,4-diyl which may have a substituent, X 1z and X 2z At least one of them is 1,4-phenylene which may have a substituent or cyclohexane-1,4-diyl which may have a substituent, preferably trans-cyclohexane-1,4-diyl. As the substituent that the 1,4-phenylene which may have a substituent or the cyclohexane-1,4-diyl which may have a substituent, there can be mentioned alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl and butyl, cyano groups and halogen atoms such as chlorine atoms and fluorine atoms. It is preferably unsubstituted.
[0108] In addition, from the perspective of easily expressing smectic liquid crystal properties, the polymerizable liquid crystal compound (Z) preferably has an asymmetric structure in which the portion represented by formula (Z1) in formula (Z) [hereinafter referred to as partial structure (Z1)]
[0109] -(X 1 -Y 1 -) n -X 2 - (Z1)
[0110] [Wherein, X 1z , Y 1z , X 2z and nz respectively have the same meanings as above].
[0111] Examples of the polymerizable liquid crystal compound (Z) having an asymmetric structure include a compound in which nz is 1, 1 X 1z With X 2z In addition, there can be mentioned a polymerizable liquid crystal compound (Z) having a structure different from each other. 1z The same structure, 2 X 1z For the same structure, 1 X 2z For these two X 1z Different polymerizable liquid crystal compounds (Z); 2 X 1z in and W 1z Bonded X 1z For another X 1z and X 2z Different structure, and another X 1z With X 2z are polymerizable liquid crystal compounds (Z) having the same structure as each other. 1z The same structure, 3 X 1z and 1 X 2z Any one of them is a polymerizable liquid crystal compound (Z) having a structure different from all the other three.
[0112] Y 1z Preferred are -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, a single bond, -N=N-, -CR az =CR bz -、-C≡C-、-CR az =N- or -CO-NR az -. R az and R bz Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1z More preferably, it is -CH2CH2-, -COO- or a single bond. 1z In the case of X 2z Bonded Y 1z More preferably, it is -CH2CH2- or -CH2O-.1z and X 2z When all Y have the same structure, it is preferred that there are two or more Y having different bonding forms. 1z In the case where there are multiple Ys having different bonding modes, 1z In the case of , it becomes an asymmetric structure, so there is a tendency to easily exhibit smectic liquid crystal properties.
[0113] U 2z is the above-mentioned polymerizable group. 1z It is a hydrogen atom or a polymerizable group. From the perspective of easy manufacture, easy improvement of the heat resistance of the vertical polarizing film, and easy adjustment of the adhesion between the vertical polarizing film and the substrate, the polymerizable group is preferably a (meth)acryloyloxy group. The polymerizable group may be in a polymerized state or in an unpolymerized state, preferably in an unpolymerized state.
[0114] As V 1z and V 2z Examples of the alkanediyl group include methylene, ethylene, propane-1,3-diyl, butane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, decane-1,10-diyl, tetradecane-1,14-diyl and eicosane-1,20-diyl. 1z and V 2z An alkanediyl group having 2 to 12 carbon atoms is preferred, and an alkanediyl group having 6 to 12 carbon atoms is more preferred.
[0115] Examples of the substituent that the alkanediyl group may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted straight-chain alkanediyl group.
[0116] W 1z and W 2z Independently of each other, preferably it is a single bond, -O-, -S-, -COO- or -OCOO-, more preferably it is a single bond or -O-.
[0117] The polymerizable liquid crystal compound (Z) preferably has an asymmetric molecular structure in the molecular structure, and more specifically, it is more preferably a polymerizable liquid crystal compound having the following partial structures (Aa) to (Ai). From the viewpoint of easily showing high-order smectic liquid crystal properties, it is more preferably a partial structure (Aa), (Ab) or (Ac). It should be noted that in the following (Aa) to (Ai), * represents a connecting bond (single bond).
[0118] [Chemical formula 2]
[0119]
[0120] Specific examples of the polymerizable liquid crystal compound (Z) include compounds represented by formula (A-1) to formula (A-25). When the polymerizable liquid crystal compound (Z) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.
[0121] [Chemical formula 3]
[0122]
[0123] [Chemical formula 4]
[0124]
[0125] [Chemical formula 5]
[0126]
[0127] Among them, at least one selected from the compounds represented by formula (A-2), formula (A-3), formula (A-4), formula (A-5), formula (A-6), formula (A-7), formula (A-8), formula (A-13), formula (A-14), formula (A-15), formula (A-16) and formula (A-17) is preferred. As the polymerizable liquid crystal compound (Z), one may be used alone or two or more may be used in combination.
[0128] The polymerizable liquid crystal compound (Z) can be produced by a known method described in, for example, Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156.
[0129] The polymerizable liquid crystal compound forming the vertical polarizing film is preferably a polymerizable liquid crystal compound having a maximum absorption wavelength between 300 and 400 nm. In the case where a photopolymerization initiator is included in the polymerizable liquid crystal composition, it is possible to carry out polymerization reaction and gelation of the polymerizable liquid crystal compound during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300 to 400 nm, even if it is exposed to ultraviolet light during storage, it is possible to effectively inhibit the generation of reactive species by the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species. Therefore, it is advantageous in terms of the long-term stability of the composition containing the polymerizable liquid crystal compound, and the orientation and uniformity of the film thickness of the obtained liquid crystal cured film can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, for example, chloroform and the like.
[0130] From the viewpoint of improving the orientation of the liquid crystal compound, the content ratio of the liquid crystal compound in the liquid crystal composition forming the vertical polarizing film is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, preferably 99.5 parts by mass or less, more preferably 99 parts by mass or less, further preferably 94 parts by mass or less, and further preferably 92 parts by mass or less, relative to 100 parts by mass of the vertical polarizing film. The content ratio of the liquid crystal compound can be calculated as the ratio of the liquid crystal compound to 100 parts by mass of the solid content of the liquid crystal composition forming the vertical polarizing film.
[0131] <Horizontal polarizing film>
[0132] In the present invention, the horizontal polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye, and refers to a film in which the polymerizable liquid crystal film is horizontally aligned in a certain direction in the film plane.
[0133] <Dichroic Pigments>
[0134] As a dichroic pigment, it is preferred that the vertical polarizing film and the horizontal polarizing film have an absorption maximum wavelength (λMAX) in the range of wavelength 300 to 750nm. As such a dichroic pigment, for example, acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments and anthraquinone pigments can be cited, among which azo pigments are preferred. As azo pigments, monoazo pigments, disazo pigments, triazo pigments, tetrazo pigments and stilbene azo pigments can be cited, preferably monoazo pigments and disazo pigments. The dichroic pigment can be used alone or in combination, but in the case where polarization characteristics are required in the entire visible light region, it is preferred to combine two or more dichroic pigments. For example, a dichroic pigment having an absorption maximum wavelength at more than 400nm and less than 500nm and a dichroic pigment having an absorption maximum wavelength at more than 500nm and less than 600nm can be enumerated, or a dichroic pigment having an absorption maximum wavelength at more than 500nm and less than 600nm and a dichroic pigment having an absorption maximum wavelength at more than 600nm and less than 700nm can be combined, etc. It should be noted that the absorbance of the dichroic pigment can be measured by a spectrophotometer, for example, in a state where the solvent dissolving the dichroic pigment such as chloroform is dissolved.
[0135] The dichroic pigment constituting the vertical polarizing film and the horizontal polarizing film may be used in one kind only or in combination of two or more kinds. The dichroic pigment may be used in a properly selected type and / or content so as to be a complementary color for offsetting the colored internal reflected light slightly emitted obliquely from the first phase element side when displaying black.
[0136] Examples of the azo dye include compounds represented by formula (I) (hereinafter, sometimes referred to as "compound (I)"),
[0137] A 1 (-N=NA 2 ) p -N=NA 3 (I)
[0138] [In formula (I),
[0139] A 1 and A 3 A represents independently of each other a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. 2 represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of A 2 They may be the same or different from each other. In the range showing absorption in the visible region, the -N=N- bond may be replaced by a -C=C-, -COO-, -NHCO-, or -N=CH- bond].
[0140] Examples of the monovalent heterocyclic group include groups obtained by removing one hydrogen atom from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole and benzoxazole. Examples of the divalent heterocyclic group include groups obtained by removing two hydrogen atoms from the above heterocyclic compounds.
[0141] As A 1 and A 3 The phenyl, naphthyl and monovalent heterocyclic groups in A 2 The substituents which the p-phenylene, naphthalene-1,4-diyl and divalent heterocyclic group may optionally have include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms having a polymerizable group, an alkenyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 20 carbon atoms such as methoxy, ethoxy and butoxy; an alkoxy group having 1 to 20 carbon atoms having a polymerizable group; a fluoroalkyl group having 1 to 4 carbon atoms such as trifluoromethyl; a cyano group; a nitro group; a halogen atom; a substituted or unsubstituted amino group such as amino, diethylamino and pyrrolidinyl (a substituted amino group refers to an amino group having 1 or 2 alkyl groups having 1 to 6 carbon atoms, an amino group having 1 or 2 alkyl groups having 1 to 6 carbon atoms having a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. An unsubstituted amino group is -NH2.) and the like. In addition, here, as said polymerizable group, an acryloyl group, a methacryloyl group, an acryloyloxy group, a methacryloyloxy group, etc. are mentioned.
[0142] Among the compounds (I), compounds represented by any one of the following formulae (I-1) to (I-8) are preferred.
[0143] [Chemical formula 6]
[0144]
[0145] [In formulas (I-1) to (I-8),
[0146] B 1 ~B 30 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the definitions of the substituted amino group and the unsubstituted amino group are as described above), a chlorine atom or a trifluoromethyl group.
[0147] n1 to n4 represent integers of 0 to 3 independently of each other.
[0148] When n1 is greater than 2, multiple B 2 They can be the same or different from each other.
[0149] When n2 is greater than 2, multiple B 6 They can be the same or different from each other.
[0150] When n3 is greater than 2, multiple B 9 They can be the same or different from each other.
[0151] When n4 is 2 or more, multiple B 14 They may be the same or different from each other.]
[0152] From the viewpoint of making the orientation of the dichroic dye good, the content of the dichroic dye in the liquid crystal composition forming the vertical polarizing film and the horizontal polarizing film is preferably 0.1 mass part or more and 30 mass parts or less, more preferably 0.1 mass part or more and 20 mass parts or less, further preferably 0.1 mass part or more and 10 mass parts or less, and particularly preferably 0.1 mass part or more and 7 mass parts or less, relative to 100 mass parts of the solid content of the liquid crystal composition. If the content of the dichroic dye is within this range, it is not easy to disturb the liquid crystal orientation of the liquid crystal compound, so it is preferred.
[0153] In the present invention, the liquid crystal composition used in the formation of the vertical polarizing film and the horizontal polarizing film may contain components other than the dichroic pigment and the polymerizable liquid crystal compound. Such components include, for example, a polymerization initiator, a leveling agent, a solvent, an antioxidant, a photosensitizer, etc. These components may be used alone or in combination of two or more.
[0154] (Polymerization initiator)
[0155] The polymerization initiator is a compound that can initiate a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferred.
[0156] Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts.
[0157] Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4′-methyldiphenyl sulfide, 3,3′,4,4′-tetrakis(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0158] Examples of the alkylphenone compound include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-〔4-(2-hydroxyethoxy)phenyl〕propane-1-one, 1-hydroxycyclohexylphenyl ketone and oligomers of 2-hydroxy-2-methyl-1-〔4-(1-methylvinyl)phenyl〕propane-1-one.
[0159] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0160] Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)] [vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)vinyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)vinyl]-1,3,5-triazine, etc.
[0161] The polymerization initiator can be a commercially available product. Examples of the commercially available polymerization initiator include Irgacure (registered trademark) 907, 184, 651, 819, 250 and 369 (BASF); Seikuol (registered trademark) BZ, Z and BEE (Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 and UVI-6992 (Nippon Kayaku Co., Ltd.); Adeka Optomer SP-152 and SP-170 (ADEKA Co., Ltd.); TAZ-A and TAZ-PP (DKSH Japan Co., Ltd.); and TAZ-104 (Sanwa Chemical Co., Ltd.).
[0162] From the viewpoint of not easily disturbing the orientation of the polymerizable liquid crystal compound, the content of the polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 8 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0163] (Leveling agent)
[0164] The leveling agent is a substance that has the function of adjusting the fluidity of the liquid crystal composition and making the vertical polarization film and the horizontal alignment film flatter, and examples thereof include surfactants. Preferred leveling agents include leveling agents with polyacrylate compounds as the main component and leveling agents with fluorine-containing compounds as the main component.
[0165] Examples of the leveling agent containing a polyacrylate compound as a main component include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-358N, BYK-361N, BYK-380, BYK-381, and BYK-392 (BYK Chemie).
[0166] As leveling agents having a fluorine atom-containing compound as a main component, there can be mentioned Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-471, F-477, F-479, F-482, and F-483 (DIC Corporation); Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, and SA-100 (AGC SEMICHEMICAL Co., Ltd.); E1830 and E5844 (DAIKIN FINE CHEMICAL Co., Ltd.); Eftop EF301, EF303, EF351, and EF352 (Mitsubishi Materials Electronic Chemicals Co., Ltd.), and the like.
[0167] The content of the leveling agent is preferably 0.01 parts by mass or more relative to 100 parts by mass of the polymerizable liquid crystal compound, more preferably 0.1 parts by mass or more, preferably 5 parts by mass or less, and more preferably 3 parts by mass or less. If the content of the leveling agent is within the above range, there is a tendency for the resulting liquid crystal cured film to become smoother, so it is preferred. If the content of the leveling agent exceeds the above range relative to the polymerizable liquid crystal compound, the resulting liquid crystal cured film is prone to uneven and disordered orientation, so it is not preferred. The vertical polarizing film and the horizontal polarizing film may contain more than two kinds of leveling agents.
[0168] (Solvent)
[0169] As the solvent, one that can completely dissolve the polymerizable liquid crystal compound is preferred, and one that is inactive to the polymerization reaction is also preferred.
[0170] As the solvent, there can be mentioned alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane and heptane; aromatic hydrocarbon solvents such as toluene and xylene, nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene, etc. These solvents can be used alone or in combination of two or more.
[0171] The content of the solvent is preferably 50 to 98% by mass relative to the total amount of the liquid crystal composition. In other words, the ratio of the vertical polarizing film and horizontal polarizing film components is preferably 2 to 50% by mass relative to the total amount of the liquid crystal composition.
[0172] If the solid content is 50% by mass or less relative to the total amount of the liquid crystal composition, the viscosity of the liquid crystal composition becomes low, so that the thickness of the liquid crystal cured film becomes roughly uniform, and there is a tendency that the vertical polarizing film and the horizontal polarizing film are not easily uneven. In addition, the solid content can be determined in consideration of the thickness of the vertical polarizing film and the horizontal polarizing film to be manufactured.
[0173] (Antioxidant)
[0174] By adding an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. As an antioxidant, it can be a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or it can be a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the orientation of the polymerizable liquid crystal compound, the content of the antioxidant is generally 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0175] The antioxidants can be used alone or in combination of two or more.
[0176] (Photosensitizer)
[0177] By using a photosensitizer, the photopolymerization initiator can be made highly sensitive. Examples of the photosensitizer include xanthones such as xanthones and thioxanthones; anthracenes and anthracenes having substituents such as alkyl ether groups; phenothiazines; and rubrene. The photosensitizer can be used alone or in combination of two or more. The content of the photosensitizer is generally 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0178] (Method for manufacturing vertical polarizing film and horizontal polarizing film)
[0179] In the present invention, the vertical polarizing film and the horizontal polarizing film can be manufactured, for example, by a method including the following steps:
[0180] A step of obtaining a liquid crystal composition by stirring a polymerizable liquid crystal compound and a dichroic dye and, if necessary, an additive such as a solvent at a predetermined temperature;
[0181] a step of forming a coating film of the liquid crystal composition; and
[0182] A step of drying the coating film to form a dried coating film.
[0183] The temperature when stirring the polymerizable liquid crystal compound and the dichroic dye and additives such as a solvent according to the case is usually 0 to 100° C., preferably 10 to 90° C. The stirring method is not particularly limited, and stirring can be performed by a conventionally known method.
[0184] The coating film of the liquid crystal composition can be formed by, for example, applying the liquid crystal composition on a substrate or an alignment film.
[0185] As the substrate, for example, a glass substrate, a film substrate, etc. can be cited. From the viewpoint of processability, a resin film substrate is preferred. As the resin constituting the film substrate, for example, polyolefins such as polyethylene, polypropylene and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; plastics such as polyphenylene sulfide and polyphenylene ether. Such resins can be made into a substrate by a known method such as a solvent casting method and a melt extrusion method. The surface of the substrate may have a protective layer formed by an acrylic resin, a methacrylic resin, an epoxy resin, an oxetane resin, a urethane resin, a melamine resin, etc., and a surface treatment such as a release treatment such as a silicone treatment, a corona treatment, and a plasma treatment may also be performed.
[0186] As the substrate, commercially available products can be used. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fujifilm Corporation, such as FUJITACFILM; cellulose ester substrates manufactured by Konicaminolta Corporation, such as "KC8UX2M", "KC8UY" and "KC4UY", etc. As commercially available cyclic olefin resins, examples include cyclic olefin resins manufactured by Ticona (Germany), such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation, such as "ARTON (registered trademark)"; cyclic olefin resins manufactured by ZEON Corporation, such as "ZEONOR (Registered Trademark)" and "ZEONEX (Registered Trademark)"; cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "APEL (Registered Trademark)". Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin-based resin substrates include cyclic olefin-based resin substrates such as “ESCENA (registered trademark)” and “SCA40 (registered trademark)” manufactured by Sekisui Chemical Co., Ltd.; cyclic olefin-based resin substrates such as “ZEONOR FILM (registered trademark)” manufactured by OPTES Corporation; and cyclic olefin-based resin substrates such as “ARTON FILM (registered trademark)” manufactured by JSR Corporation.
[0187] The thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm, from the viewpoint of ease of substrate peeling and substrate handling.
[0188] Examples of a method for applying the liquid crystal composition to a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, and printing methods such as flexographic methods.
[0189] Next, the solvent is removed by drying, thereby forming a dry coating. As a drying method, natural drying, ventilation drying, heating drying and reduced pressure drying can be cited. At this time, by heating the coating obtained by the liquid crystal composition, the solvent can be dried and removed from the coating, and the liquid crystal compound is oriented in a vertical direction or a horizontal direction relative to the coating plane. The heating temperature of the coating can be appropriately determined by considering the material of the liquid crystal compound used and the substrate forming the coating, but in order to make the liquid crystal compound phase transition to the liquid crystal layer state, it is necessary to be a temperature above the liquid crystal phase transition temperature. In order to remove the solvent contained in the liquid crystal composition while making the liquid crystal compound become a vertical or horizontal orientation state, for example, it can be heated to a temperature above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the liquid crystal compound contained in the above-mentioned liquid crystal composition.
[0190] It should be noted that the liquid crystal phase transition temperature can be measured, for example, using a polarizing microscope, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analysis device (TG-DTA) and the like equipped with a temperature regulating station. In addition, when two or more liquid crystal compounds are used in combination, the above-mentioned phase transition temperature refers to a mixture of polymerizable liquid crystal compounds formed by mixing all polymerizable liquid crystal compounds constituting the liquid crystal composition in the same ratio as the composition in the liquid crystal composition, and the temperature measured in the same manner as the case of using one polymerizable liquid crystal compound. It should be noted that it is known that the liquid crystal phase transition temperature of the polymerizable liquid crystal compound in the above-mentioned liquid crystal composition is sometimes lower than the liquid crystal phase transition temperature as a polymerizable liquid crystal compound monomer.
[0191] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc., and is usually 15 seconds to 10 minutes, preferably 0.5 to 5 minutes.
[0192] In the case of using a polymerizable liquid crystal compound as a liquid crystal compound, next, in the obtained dry coating, while maintaining the vertical or horizontal orientation state of the polymerizable liquid crystal compound, the polymerizable liquid crystal compound is polymerized to form a vertical polarizing film. As a polymerization method, thermal polymerization or photopolymerization can be cited, and from the viewpoint of easy control of the polymerization reaction, photopolymerization is preferred. In photopolymerization, as the light irradiated to the dry coating, it can be appropriately selected according to the type of photopolymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount. As a specific example, one or more light selected from visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays and active electron beams can be cited. Among them, from the aspect of easy control of the progress of the polymerization reaction, as a photopolymerization device, a device widely used in the art can be used, preferably ultraviolet light, preferably pre-selecting the type of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition, so that photopolymerization can be performed by ultraviolet light. In addition, during polymerization, the polymerization temperature can also be controlled by cooling the dried coating film using appropriate cooling means while irradiating light. By adopting such cooling means, if the polymerization of the polymerizable liquid crystal compound is carried out at a lower temperature, a vertical or horizontal polarizing film can be properly formed even if a substrate with low heat resistance is used for the substrate. In addition, by increasing the polymerization temperature within a range that does not cause adverse conditions caused by heat during light irradiation (deformation caused by heat of the substrate, etc.), the polymerization reaction can also be promoted. During photopolymerization, a patterned vertical or horizontal polarizing film can also be obtained by shielding, developing, etc.
[0193] As the light source of the above-mentioned active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0194] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and further preferably 0.1 second to 1 minute. If irradiated once or more times with such ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 .
[0195] The thickness of the vertical polarizing film and the horizontal polarizing film can be appropriately selected according to the display device to which it is applied, preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm, further preferably 0.2 to 3 μm, further preferably 0.5 to 5 μm, and particularly preferably 0.5 to 3 μm. If the thickness of the vertical polarizing film and the horizontal polarizing film is within the above range, the laminate can be made thinner. The thickness of the vertical polarizing film and the horizontal polarizing film can be measured, for example, using a laser microscope, a stylus film thickness meter, or the like.
[0196] In one embodiment of the present invention, a coating of a liquid crystal composition is formed on an alignment film. The alignment film has an alignment restriction force that allows the liquid crystal compound to be oriented in a desired direction. Among them, an alignment film having an alignment restriction force that allows the liquid crystal compound to be oriented in a horizontal direction is sometimes referred to as a horizontal alignment film, and an alignment film having an alignment restriction force that allows the liquid crystal compound to be oriented in a vertical direction is sometimes referred to as a vertical alignment film. The alignment restriction force can be arbitrarily adjusted according to the type, surface state, friction conditions, etc. of the alignment film. When the alignment film is formed of a photo-aligned polymer, it can be arbitrarily adjusted according to polarized light irradiation conditions, etc.
[0197] The alignment film preferably has solvent resistance so as not to be dissolved by application of the liquid crystal composition or the like, and also has heat resistance in a heating treatment for removing the solvent or aligning the liquid crystal compound described later.
[0198] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and their hydrolyzates, i.e., polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.
[0199] The oriented film containing the oriented polymer is usually obtained by applying a composition in which the oriented polymer is dissolved in a solvent (hereinafter, sometimes referred to as an "oriented polymer composition") to a substrate and removing the solvent, or applying the oriented polymer composition to a substrate and removing the solvent, and rubbing (rubbing method). As the solvent, the same solvent as the solvent exemplified above as a solvent that can be used for the liquid crystal composition can be cited.
[0200] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably about 0.1% to 20%, more preferably about 0.1% to 10%, based on the solid content of the solution.
[0201] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTOMER (registered trademark, manufactured by JSR Corporation).
[0202] As a method for applying the oriented polymer composition on the substrate, the same method as exemplified as the method for applying the liquid crystal composition on the substrate can be mentioned.
[0203] Examples of a method for removing the solvent contained in the oriented polymer composition include a natural drying method, a ventilation drying method, a heat drying method, and a reduced pressure drying method.
[0204] The photo-alignment film used to form the vertical polarization film and the horizontal polarization film is generally obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as "photo-alignment film forming composition") to a substrate, removing the solvent, and then irradiating with ultraviolet light. The ultraviolet light irradiated here is generally non-polarized light.
[0205] Photoreactive groups refer to groups that generate liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules generated by light irradiation, which are the source of liquid crystal orientation ability, can be cited. Among them, groups participating in dimerization reaction or photocrosslinking reaction are preferred from the perspective of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from carbon-carbon double bond (C=C bond), carbon-nitrogen double bond (C=N bond), nitrogen-nitrogen double bond (N=N bond) and carbon-oxygen double bond (C=O bond).
[0206] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazolyl, stilbazolyl, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo groups, disazo groups, formazan groups, and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl groups.
[0207] Among them, photoreactive groups that participate in the photodimerization reaction are preferred, and cinnamoyl and chalcone groups are preferred from the perspective of a small amount of polarized light irradiation required for photo-alignment and an excellent photo-alignment film with good thermal stability and temporal stability. As a polymer having a photoreactive group, a polymer having a cinnamoyl group such as a cinnamic acid structure at the terminal of the polymer side chain is particularly preferred.
[0208] By applying the photo-alignment film-forming composition on a substrate, a photo-alignment inducing layer can be formed on the substrate. As the solvent contained in the composition, the same solvents as those previously exemplified as solvents that can be used in the liquid crystal composition can be cited, and can be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.
[0209] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film can contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly impair the properties of the photo-alignment film.
[0210] As a method for applying the photo-alignment film-forming composition to a substrate, the same method as the method for applying the oriented polymer composition to a substrate can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0211] In order to irradiate polarized light, it can be a form of directly irradiating polarized light UV to the substance obtained by removing the solvent from the composition for forming a photo-alignment film applied on the substrate, or it can be a form of irradiating polarized light from the substrate side and transmitting the polarized light. In addition, the polarized light is particularly preferably substantially parallel light. The wavelength of the polarized light irradiated is the wavelength of the wavelength region in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400nm is particularly preferred. As a light source for the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among them, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because the luminous intensity of ultraviolet rays with a wavelength of 313nm is large. The light from the above-mentioned light source is irradiated through an appropriate polarizer, thereby enabling the irradiation of polarized light UV. As the polarizing plate, a polarizing filter, a polarizing prism such as a Glan-Thompson prism or a Glan-Taylor prism, or a wire-grid type polarizing plate can be used.
[0212] In addition, when rubbing or polarized light irradiation is performed, if shielding is performed, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.
[0213] A grooved alignment film is a film having a concavo-convex pattern or multiple grooves on the film surface. When a liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules are aligned in the direction along the grooves.
[0214] As methods for obtaining a groove-oriented film, the following methods can be cited: a method in which a surface of a photosensitive polyimide film is exposed through an exposure mask having a slit in a pattern shape, and then developing and rinsing are performed to form a concave-convex pattern; a method in which a layer of a pre-cured UV-curable resin is formed on a plate-shaped original disk having grooves on its surface, and the formed resin layer is transferred to a substrate and then cured; and a method in which a rolled original disk having a plurality of grooves is pressed onto a film of a pre-cured UV-curable resin formed on a substrate to form concave-convex and concave, and then cured.
[0215] As materials that exhibit an alignment regulating force that orients the liquid crystal compound in the vertical and horizontal directions relative to the coating plane, in addition to the above-mentioned alignment polymers, fluorine-based polymers such as perfluoroalkyl and silane compounds, and polysiloxane compounds obtained by their condensation reaction can be used.
[0216] When a silane compound is used as a material for forming an alignment film, from the viewpoint of easily reducing the surface tension and easily improving the adhesion with the layer adjacent to the alignment film, a compound containing Si element and C element in the constituent elements is preferably used, and the silane compound can be appropriately used. By using a silane compound, the orientation restriction force can be improved. These silane compounds can be used alone, in combination of two or more, or mixed with other materials.
[0217] The thickness of the alignment film (alignment film or photoalignment film containing an aligning polymer) is usually in the range of 10 to 10000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm or less, further preferably 10 to 300 nm, particularly preferably 50 to 250 nm.
[0218] In another embodiment of the present invention, a coating of a liquid crystal composition can be formed directly on a substrate without an orientation film. In this embodiment, a liquid crystal composition for forming a vertical polarizing film generally contains an orientation promoter. In the present invention, an orientation promoter refers to a material that promotes liquid crystal orientation of a liquid crystal compound in a desired direction. As an orientation promoter that promotes the orientation of a liquid crystal compound, ionic compounds containing non-metallic atoms and non-ionic silane compounds can be cited. The liquid crystal composition that forms a vertical polarizing film preferably contains at least one of an ionic compound containing non-metallic atoms and a non-ionic silane compound, and more preferably contains both an ionic compound containing non-metallic atoms and a non-ionic silane compound.
[0219] <First Phase Element>
[0220] In the present invention, the first phase element showing the phase difference in the plane is usually a stretched film (phase difference film), and can also be a phase difference film formed by a composition containing a polymerizable liquid crystal compound (hereinafter also referred to as a "polymerizable liquid crystal composition"), etc. From the viewpoint of large film thickness and strength, a stretched film is preferred.
[0221] In addition, the first phase element preferably has positive wavelength dispersion, but may also have reverse wavelength dispersion.
[0222] The film stretched in at least one direction is not particularly limited. From the viewpoint of dimensional stability and heat resistance stability, a film having a glass transition temperature (Tg) of 80 to 200°C is preferred. Examples thereof include polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; fluorinated polyolefin resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyvinyl fluoride; polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / ethylene isophthalate copolymers. Polyester resins such as nylon 6, nylon 6,6 and other polyamides; vinyl polymers such as polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate, cellulose diacetate, and cellophane; (meth) acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; and films composed of polystyrene, polycarbonate, polyarylate, and polyimide. From the viewpoint of dimensional stability, it is preferably a film comprising a vinyl polymer, a (meth) acrylic resin, or a polyolefin resin, and more preferably a film comprising a cycloolefin resin. The glass transition temperature can be measured, for example, by DSC (differential scanning calorimetry).
[0223] In the case where the first phase element is a stretched film, the film can be manufactured, for example, by a method comprising the following steps:
[0224] a step of forming the above-mentioned resin, which may contain additives such as an antioxidant and a UV absorber, into a film; and
[0225] A step of stretching the film.
[0226] Examples of a method for molding a resin into a film include known methods such as a melt extrusion method, a hot press molding method, an injection molding method, and a solvent casting method.
[0227] As a method for stretching the film, for example, uniaxial stretching or biaxial stretching can be cited. As the stretching direction, the mechanical travel direction (MD) of the unstretched film, the direction (TD) orthogonal thereto, and the direction oblique to the mechanical travel direction (MD) can be cited. Uniaxial stretching can be performed between rollers with different circumferential speeds, or uniaxial stretching can be performed using a hot roller. Biaxial stretching can be a simultaneous biaxial stretching in which stretching is performed simultaneously in two stretching directions, or a sequential biaxial stretching in which stretching is performed in other directions after stretching in a specified direction. The stretching process can be performed in the following manner: using, for example, two or more pairs of clamping rollers with a larger circumferential speed on the outlet side, stretching along the long side direction (mechanical travel direction: MD), or holding the two side ends of the unstretched film with a chuck, and extending in a direction (TD) orthogonal to the mechanical travel direction. In addition, as a method for stretching in an oblique direction, for example, the following method can be cited: preparing a film roll obtained by winding a long film into a roll, continuously unwinding the film from the film roll, conveying the unwound film, and stretching it along the longitudinal direction of the film and in an oblique direction inclined at a desired angle while heating. The stretching ratio is usually 3 to 8 times. It should be noted that the stretching ratio in biaxial stretching refers to the stretching ratio in the direction with a larger stretching ratio.
[0228] The stretched film may be subjected to a surface treatment known in the art, such as a plasma treatment, a corona treatment, an ozone treatment, and an ultraviolet irradiation treatment, before or after the stretching treatment.
[0229] The film stretched in at least one direction as described above can be a commercially available film. Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany) such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation such as "ARTON (registered trademark)"; cyclic olefin resins manufactured by ZEON Corporation of Japan such as "ZEONOR (registered trademark)" and "ZEONEX (registered trademark)"; cyclic olefin resins manufactured by Mitsui Chemicals, Inc. such as "APEL (registered trademark)". Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates such as "ESCENA (registered trademark)" and "S CA40 (registered trademark)" manufactured by Sekisui Chemical Co., Ltd., cyclic olefin resin substrates such as "ZEONOR FILM (registered trademark)" manufactured by OPTES Co., Ltd., and cyclic olefin resin substrates such as "ARTON FILM (registered trademark)" manufactured by JSR Corporation. Examples of commercially available cellulose ester substrates include cellulose ester substrates such as FUJITAC FILM manufactured by Fujifilm Corporation, and cellulose ester substrates such as "KC8UX2M", "KC8UY" and "KC4UY" manufactured by Konica Minolta Co., Ltd.
[0230] In the case where the first phase element is a phase difference film formed by a polymerizable liquid crystal composition, the composition includes a polymerizable liquid crystal compound. As a polymerizable liquid crystal compound capable of constituting the first phase element, generally, a polymer (cured product) obtained by polymerizing the polymerizable liquid crystal compound alone in a state oriented in a specific direction can include a polymerizable liquid crystal compound showing reverse wavelength dispersion and a polymerizable liquid crystal compound showing positive wavelength dispersion. In the first phase element, only any one polymerizable liquid crystal compound can be used, or two polymerizable liquid crystal compounds can be mixed and used. In addition, a polymerizable liquid crystal compound can be used alone or in combination of more than two. As a polymerizable liquid crystal compound showing positive wavelength dispersion, specifically, a compound identical to the compound exemplified in the project of the vertical polarizing film can be cited. As a polymerizable liquid crystal compound showing reverse wavelength dispersion, for example, a polymerizable liquid crystal compound described later in the second phase element can be cited.
[0231] From the viewpoint of thinning the laminate and improving the bendability, the thickness of the first phase element is usually 200 μm or less, preferably 100 μm or less, and more preferably 50 μm or less. In addition, the lower limit of the thickness of the first phase element is not particularly limited, but if it is too thin, the strength is sometimes reduced, so in the case of a phase difference film, it is usually 5 μm or more, 10 μm to 40 μm, and preferably 15 μm to 35 μm. In addition, in the case of a phase difference film, it is usually 1 μm or more, usually 1 μm to 10 μm, and preferably 1 μm to 5 μm.
[0232] <Polarizing Plate>
[0233] As the polarizer, it can be a stretched film adsorbed with a pigment having optical anisotropy, or it can be a polymerizable liquid crystal alignment film. As the stretched film, for example, a film including a film coated with a pigment having optical anisotropy, etc. can be cited. As the pigment having optical anisotropy, for example, a dichroic pigment can be cited.
[0234] A stretched film adsorbed with a dye having optical anisotropy is usually produced by clamping a transparent protective film on at least one side of a polarizer with the aid of an adhesive, and the polarizer is produced through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film; a step of adsorbing the dichroic dye by dyeing the polyvinyl alcohol resin film with a dichroic dye; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic dye with an aqueous boric acid solution; and a step of washing with water after the treatment with the aqueous boric acid solution.
[0235] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0236] The saponification degree of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal and polyvinyl acetal modified with aldehydes may be used. The polymerization degree of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0237] The film obtained by forming such a polyvinyl alcohol-based resin into a film is used as a raw material film of a polarizing film. The method of forming a polyvinyl alcohol-based resin into a film is not particularly limited, and the film can be formed by a known method. The film thickness of the polyvinyl alcohol-based raw material film can be set to about 10 to 150 μm, for example.
[0238] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing with a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in these multiple stages. During the uniaxial stretching, the uniaxial stretching can be performed between rollers with different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen using a solvent. The stretching ratio is usually about 3 to 8 times.
[0239] The polyvinyl alcohol-based resin film is dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.
[0240] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As dichroic organic dyes, dichroic direct dyes containing diazo compounds such as CIDIRECT RED 39 and dichroic direct dyes containing compounds such as triazo and tetrakis azo can be cited. The polyvinyl alcohol-based resin film is preferably immersed in water before dyeing.
[0241] When iodine is used as a dichroic pigment, a method of dyeing by immersing a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide is generally adopted. The content of iodine in the aqueous solution is generally about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is generally about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used in dyeing is generally about 20 to 40°C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 20 to 1,800 seconds.
[0242] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye is generally adopted. The content of the dichroic organic dye in the aqueous solution is generally 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.
[0243] Boric acid treatment after dyeing with a dichroic pigment can usually be carried out by immersing the dyed polyvinyl alcohol resin film in an aqueous solution of boric acid. The content of boric acid in the aqueous solution of boric acid is usually about 2 to 15 parts by mass relative to 100 parts by mass of water, preferably 5 to 12 parts by mass. When iodine is used as a dichroic pigment, the aqueous solution of boric acid preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass relative to 100 parts by mass of water, preferably 5 to 12 parts by mass. The immersion time in the aqueous solution of boric acid is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0244] The polyvinyl alcohol-based resin film after the boric acid treatment is usually subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of the water in the water washing treatment is usually about 5 to 40° C. In addition, the immersion time is usually about 1 to 120 seconds.
[0245] After washing, drying treatment is performed to obtain a polarizer. Drying treatment can be performed using, for example, a hot air dryer or a far infrared heater. The temperature of the drying treatment is usually about 30 to 100° C., preferably 50 to 80° C. The time of the drying treatment is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying treatment, the moisture content of the polarizer is reduced to a practical level. Its moisture content is usually about 5 to 20% by weight, preferably 8 to 15% by weight. If the moisture content is within the above range, a polarizer with moderate flexibility and excellent thermal stability can be obtained.
[0246] The thickness of the polarizing plate obtained by the above method is preferably 5 to 40 μm, usually 20 μm or less, preferably 15 μm or less, and more preferably 0.5 to 10 μm.
[0247] Examples of the film coated with a dye having optical anisotropy include a film coated with a composition containing a dichroic dye having liquid crystal properties or a composition containing a dichroic dye and polymerizable liquid crystal.
[0248] The film coated with the optically anisotropic dye is preferably thinner, but if it is too thin, the strength tends to decrease and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0249] Specific examples of the film coated with a dye having optical anisotropy include films described in JP-A-2012-33249 and the like.
[0250] <Second Phase Element>
[0251] The laminate of the present invention includes a second phase element. The second phase element can also be used as a separate phase element. In addition, the second phase element can also be assembled as one of the phase elements constituting the multiple phase difference plate, in which case, another phase element different from the second phase element is included in the multiple phase difference plate. The second phase element is a phase element that shows a phase difference in the plane or thickness direction. Specifically, for example, it can be a phase difference film that shows a phase difference in the plane or thickness direction and is formed by stretching a thermoplastic resin film, etc.; a phase difference film that is composed of a cured film of a composition comprising a polymerizable liquid crystal compound and shows a phase difference in the plane or thickness direction, etc.
[0252] In one embodiment of the present invention, a phase element showing an in-plane phase difference is preferably included as the second phase element. In this case, the second phase element preferably satisfies the following formula (9), that is, the in-plane phase difference Rei at a wavelength of 550nm i (550) is greater than 120 nm and less than 160 nm:
[0253] 120nm≤Re ii (550)≤160nm (9)
[0254] [In formula (9), Re ii (λ) represents the in-plane phase difference value of the second phase element at a wavelength of λ nm].
[0255] Such a phase element functions as a so-called λ / 4 plate.
[0256] In the present invention, if the in-plane phase difference Rei of the second phase element is i (550) is within the range of formula (9), then when applied to an organic EL display device, internal reflected light during black display is suppressed. The in-plane phase difference Rei of the second phase element is i (550) is more preferably 130nm≤Re ii (550)≤150nm, more preferably 135nm≤Rei i The in-plane phase difference Rei of the second phase element is i The adjustment method and measurement method of (550) are the same as those described in the in-plane phase difference of the first phase element.
[0257] When the second phase element is included alone, the second phase element preferably satisfies the following formula (10):
[0258] Re ii(450) / Re ii (550)<1.00 (10)
[0259] [In formula (10), Re ii (λ) has the same meaning as in the above formula (9).
[0260] When the second phase element satisfies the above formula (10), the second phase element shows a so-called reverse wavelength dispersion in which the in-plane phase difference value at a short wavelength is smaller than the in-plane phase difference value at a long wavelength. When the laminated body of the present invention including the second phase element is applied to an organic EL display device, it can effectively suppress the internal reflection of visible light in a wide wavelength range in black display. In addition, even if the internal reflected light leaks slightly, its coloring is suppressed. The Rei of the second phase element is i (450) / Rei i (550) is more preferably 0.90 or less, and further preferably 0.85 or less. i (450) / Rei i The lower limit of (550) is not particularly limited, and is, for example, 0.7 or more. i (450) and Rei i (550) can be adjusted in the same manner as Re(450) and Re(550) of the first phase element, and can be measured using the same method.
[0261] In the present invention, the angle between the slow axis of the second phase element and the absorption axis of the polarizer is preferably greater than 25° and less than 65°, or greater than 125° and less than 155°. When the angle between the slow axis of the second phase element and the absorption axis of the polarizer satisfies the above range, the second phase element can become a so-called 1 / 4 wavelength plate (λ / 4 plate) capable of converting linear polarized light into circularly polarized light. Therefore, if the second phase element is a λ / 4 plate satisfying formula (9), the second phase element and the polarizer together constitute a so-called circular polarization plate. The circular polarization plate emits non-polarized light incident from the polarizer side as circularly polarized light from the second phase element side. When the angle between the slow axis of the second phase element and the absorption axis of the polarizer satisfies the above range, when the laminate including the second phase element is applied to an organic EL display device, the coloring of the internal reflected light during black display is further suppressed. The angle between the slow axis of the second phase element and the absorption axis of the polarizer is more preferably greater than 35° and less than 55°, and ideally 45°. In addition, the angle is more preferably in the range of 125° to 145°, and ideally 135°. The angle between the slow axis of the second phase element and the absorption axis of the polarizer can be adjusted in the same manner as the angle between the slow axis of the first phase element and the absorption axis of the polarizer, and can also be measured in the same manner.
[0262] As thermoplastic resin films or polymerizable liquid crystal compounds that can be used for the second phase element, there can be cited substances that are the same as the thermoplastic resin films and polymerizable liquid crystal compounds that can be used for the first phase element, vertical polarizing film, and horizontal polarizing film, and can be produced in the same way as the first phase element, vertical polarizing film, and horizontal polarizing film.
[0263] As the polymerizable liquid crystal compound, any of a compound showing positive wavelength dispersion and a compound showing reverse wavelength dispersion can be used. As the compound showing positive wavelength dispersion, for example, the same compound as the compound exemplified in the item of the vertical polarizing film can be used. In addition, as the polymerizable liquid crystal compound showing reverse wavelength dispersion, for example, a compound represented by the following formula (X) can be used.
[0264] [Chemical formula 7]
[0265]
[0266] In formula (X), Ar represents a divalent group containing an aromatic group which may have a substituent. The aromatic group referred to herein refers to a group in which the number of π electrons possessed by the ring structure is [4n+2] according to the Huckel rule, for example, an Ar group as exemplified in the following (Ar-1) to (Ar-23) may have two or more π electrons via a divalent linking group. Here, n represents an integer. In the case where a ring structure is formed by containing heteroatoms such as -N= and -S-, the case where the non-covalent bond electron pairs on these heteroatoms satisfy the Huckel rule and thus have aromaticity is also included. It is preferred that the aromatic group contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. The aromatic group contained in the divalent group Ar may be one or more. In the case where the aromatic group is one, the divalent group Ar may be a divalent aromatic group which may have a substituent. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a single bond or a divalent bonding group such as -CO-O- or -O-.
[0267] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom or a nitrogen atom.
[0268] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.
[0269] k and l each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 They may be the same as or different from each other.
[0270] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. In addition, hydrogen atoms contained in the alkanediyl group may be substituted with halogen atoms, and -CH2- contained in the alkanediyl group may be replaced with -O-, -S-, -SiH2-, or -C(=O)-.
[0271] P 1 and P2 Each of them independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0272] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms; more preferably is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group; and particularly preferably is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.
[0273] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.
[0274] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、-R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -, or C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or -OCOR a6-1 -. Here, R a2-1 , R a4-1 , R a6-1Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.
[0275] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -, or -OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.
[0276] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≤k+1≤6, preferably k+1=4, and more preferably k=2 and 1=2. If k=2 and 1=2, a symmetrical structure is obtained, which is preferred.
[0277] As P 1 or P 2 Examples of the polymerizable group include epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxiranyl and oxetanyl.
[0278] Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.
[0279] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring and phenanthroline ring etc. can be cited. Among them, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazolyl. In addition, when Ar includes nitrogen atom, the nitrogen atom preferably has π electrons.
[0280] In formula (X), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0281] Examples of the aromatic group represented by Ar include the following groups.
[0282] [Chemical formula 8]
[0283]
[0284] In the formulas (Ar-1) to (Ar-23), the * symbol represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0285] Q 1 and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or O-, R 2’ and R3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0286] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0287] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0288] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0289] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contain at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.
[0290] Y 1 , Y 2 and Y 3 Each independently may be a polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group which may be substituted. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.
[0291] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferably, Z is a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0292] Q 1 and Q2 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.
[0293] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0294] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic groups described above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z 0 Together, they are the above-mentioned optionally substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups, for example, benzofuran ring, benzothiazole ring, benzoxazole ring, etc.
[0295] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition used in the formation of the first phase element is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 97 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal cured film.
[0296] The polymerizable liquid crystal composition for forming the first phase element may further contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, and a photosensitizer in an amount that does not affect the effect of the present invention in addition to the polymerizable liquid crystal compound. As these components, the same components as those exemplified in the project of the vertical polarizing film can be cited, and only one of each can be used, or two or more can be used in combination.
[0297] The phase difference film formed of the polymerizable liquid crystal composition can be produced, for example, by a method including the following steps:
[0298] A step of obtaining a polymerizable liquid crystal composition by stirring a polymerizable liquid crystal compound and, if necessary, an additive such as a solvent at a predetermined temperature;
[0299] A step of coating the polymerizable liquid crystal composition on a substrate or an alignment film to obtain a coating film;
[0300] a step of drying the coating film to form a dried coating film; and
[0301] A step of irradiating the dried coating film with active energy rays to form a liquid crystal cured film.
[0302] The coating film of the polymerizable liquid crystal composition can be formed, for example, by coating the polymerizable liquid crystal composition on a substrate or an alignment film, etc. As the substrate that can be used here, the same substrate as exemplified as the substrate that can be used in the production of the vertical polarizing film can be used.
[0303] The orientation film can be appropriately selected from materials having a restraining force that orients the polymerizable liquid crystal compound in a horizontal direction relative to the plane of the coating film. The orientation restraining force can be arbitrarily adjusted according to the type of orientation layer, the surface state, the friction conditions, etc., and in the case of being formed by a photo-orientation polymer, it can be arbitrarily adjusted according to the polarized light irradiation conditions, etc. As such a material, for example, there can be cited materials described as orientation polymers for forming a coating film of a liquid crystal composition, and the liquid crystal composition forms a vertical polarizing film. The orientation film can be obtained by applying a composition comprising such a material and a solvent, such as the solvent exemplified in the item of the vertical polarizing film, to a substrate, and after removing the solvent, heating the coating film, etc., and further performing a friction treatment, a polarized ultraviolet irradiation treatment, etc. As an orientation film, from the viewpoint of quality, a photo-orientation film is preferably used.
[0304] Next, the solvent is removed by drying, etc., thereby forming a dry coating. As drying methods, natural drying, ventilation drying, heating drying, and reduced pressure drying methods can be cited. From the perspective of productivity, heating drying is preferred, and the heating temperature at this time is preferably capable of removing the solvent and is above the phase transition temperature of the polymerizable liquid crystal compound. The steps and conditions in the process are the same as those described in the project of the vertical polarizing film.
[0305] The obtained dried coating film is irradiated with active energy rays (more specifically, ultraviolet rays, etc.), and the polymerizable liquid crystal compound is polymerized while being oriented in a horizontal direction relative to the coating film plane, thereby forming an oriented liquid crystal cured film. The polymerization method is the same as the method described in the item of the vertical polarizing film.
[0306] In one embodiment of the present invention, the second phase element preferably includes a phase difference film, which is a cured film of a composition comprising a polymerizable liquid crystal compound. If the second phase element includes a phase difference film, the thickness of the laminate can be suppressed. In addition, by making the second phase element include a phase difference film, it is also possible to make a second phase element with less thermal shrinkage, excellent bending resistance, and less prone to cracking even if bent. It should be noted that in the present invention, the phase difference film as the second phase element is composed of a single layer formed by a cured film of a composition comprising a polymerizable liquid crystal compound, or a two-layer structure of the layer and the orientation layer.
[0307] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition for forming the second phase element is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal cured film.
[0308] The polymerizable liquid crystal composition used to form the second phase element may further contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, and a photosensitizer in addition to the polymerizable liquid crystal compound. As these components, the same components as those previously exemplified as components that can be included in the vertical polarizing film can be cited, and only one of each can be used, or two or more can be used in combination.
[0309] In the case where the second phase element is a cured product of a composition containing a polymerizable liquid crystal compound, its thickness is usually less than 10 μm, preferably less than 5 μm, more preferably less than 3 μm, and usually more than 0.1 μm. If the thickness of the second phase element is within the above range, it is advantageous in terms of thinning. It is easy to make the in-plane phase difference and the phase difference in the thickness direction the desired phase difference, thereby suppressing the coloring of the internal reflected light during black display. In the case where the second phase element is a thermoplastic resin film, its thickness is usually 10 μm to 50 μm, preferably 20 μm to 35 μm.
[0310] In the present invention, when the second phase element is assembled as one of the phase elements constituting the multiple phase difference plate, the composition of the multiple phase difference plate may include, for example, a combination of the above-mentioned second phase element showing a phase difference in the plane and another phase element showing a phase difference in the thickness direction; a combination of the above-mentioned second phase element showing a phase difference in the plane and another phase element showing a phase difference different from that of the second phase element in the plane, etc.
[0311] Examples of such multiple phase difference plates include:
[0312] (i) a multiple phase difference plate which is a combination of the second phase element showing a phase difference in the plane and a so-called positive C layer showing a phase difference in the thickness direction and can function as a λ / 4 plate with respect to light from the front side;
[0313] (ii) a combination of the second phase element that exhibits a phase difference in the plane and functions as a λ / 2 plate and a phase element that functions as a λ / 4 plate, and a multiple phase difference plate that is a so-called wide-band phase difference plate that can function as a λ / 4 plate with respect to light from the front in a wide wavelength range of visible light; and
[0314] (iii) A multiple phase difference plate that is a combination of the second phase element that exhibits a phase difference within the plane and can function as a λ / 4 plate and other phase elements that exhibit a phase difference within the plane and also exhibit a phase difference in the thickness direction, and can function as a λ / 4 plate with respect to light from the front.
[0315] The positive C wavelength plate can be produced from a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound. For example, when a rod-shaped polymerizable liquid crystal compound is used, the phase difference film is obtained when the compound is aligned vertically with respect to the in-plane.
[0316] Examples of positive C wave plates that can be used in combination with a second phase element that exhibits an in-plane phase difference include positive C wave plates having the optical characteristics shown in equations (11) and (13), and may further have the optical characteristics shown in equation (12).
[0317] -100nm≤Rth(550)≤-20nm (ii)
[0318] 1.00≤Rth(450) / Rth(550) (12)
[0319] nx≈ny <nz (13)
[0320] [In formulas (11) and (12), Rth(λ) represents the thickness phase difference of the positive C wavelength plate at a wavelength of λ nm, in formula (13), nx represents the refractive index in the slow axis direction in the plane, ny represents the refractive index in the fast axis direction in the plane (a direction orthogonal to the slow axis direction), and nz represents the refractive index in the thickness direction.]
[0321] As polymerizable liquid crystal compounds that can be used in the positive C wavelength plate that can satisfy the above formulas (11) and (13), as rod-shaped polymerizable liquid crystal compounds, there can be cited the same polymerizable liquid crystal compounds that can be used in the first phase element and the vertical polarization film.
[0322] As the above-mentioned wide-band phase difference plate, for example, it can be a phase difference plate formed by combining a second phase element (λ / 4 plate) having the optical characteristics shown in formula (14) and further the optical characteristics shown in formulas (16) and (17) and another phase element (λ / 2 plate) having the optical characteristics shown in formula (15) and further the optical characteristics shown in formulas (16) and (17).
[0323] 120nm<Re(550)<160nm (14)
[0324] 200nm<Re(550)<320nm (15)
[0325] Re(450) / Re(550)≥≥1.00 (16)
[0326] 1.00≥≥Re(650) / Re(550) (17)
[0327] [In equations (14) to (17), Re(λ) represents the in-plane phase difference of each phase element constituting the multiple phase difference plate at a wavelength of λ nm]
[0328] The multiple phase difference plate can show a phase difference in the plane or in the thickness direction based on the phase difference between the second phase element and the other phase element. The phase difference of the multiple phase difference plate can be obtained by directly measuring the phase difference of the multiple phase difference plate.
[0329] The second phase element and the other phase element may be subjected to a surface treatment known in the technical field, such as plasma treatment, corona treatment, ozone treatment, and ultraviolet irradiation treatment, on their surfaces.
[0330] In the laminated body of the present invention, the combination of the polarizing plate and the second phase element can function as a circular polarization plate.
[0331] The laminate of the present invention may include layers other than the first phase element, the vertical polarizing film, the polarizer, and the second phase element, as long as the effect of the laminate of the present invention is not affected. In the case where the laminate of the present invention includes other layers other than the first phase element, the vertical polarizing film, the polarizer, and the second phase element, as other layers, preferably, a bonding adhesive layer and a protective layer can be cited, and layers known in the technical field can be used.
[0332] For other layers, in order not to affect the above-mentioned effects (optical properties) that can be achieved by stacking the first phase element, the vertical polarization film, the polarizer and the second phase element in sequence, for example, the total light transmittance is preferably above 88% and / or the thickness is about 1 to 200 μm.
[0333] In the present invention, as the adhesive agent constituting the adhesive layer, for example, a pressure-sensitive adhesive, a drying-curing adhesive, and a chemical reaction adhesive can be cited. As the chemical reaction adhesive, for example, an active energy ray-curing adhesive can be cited. Such an adhesive agent can use an adhesive agent known in the technical field.
[0334] The thickness of the adhesive layer is not particularly limited because it is determined depending on the type, adhesion, etc., but is usually 0.001 μm to 40 μm, and preferably 0.01 to 20 μm from the viewpoint of processability and durability.
[0335] The laminate of the present invention may further include a protective layer, for example, on the surface of the first phase element opposite to the vertical polarizing film, the surface of the vertical polarizing film opposite to the first phase element, the surface of the polarizer on the vertical polarizing film side, the surface of the polarizer on the second phase element side, etc. Regarding the protective layer stacked on the polarizer, it is preferred to use a protective layer having an in-plane phase difference Re (550) of 0 (zero) nm at a wavelength of 550nm, or stacked on a single surface. By making the laminate of the present invention further include a protective layer, it is possible to prevent the first phase element, the vertical polarizing film, the polarizer, the second phase element, etc. from dimensional changes, breakage and cracks caused by heat and / or humidity. In addition, it is possible to prevent degradation when exposed to ultraviolet rays, etc., and it is possible to prevent damage and degradation of the surfaces of the first phase element, the vertical polarizing film, the polarizer, the second phase element, etc. during storage and transportation.
[0336] Examples of the protective layer include a hard coat layer formed by curing a composition containing a reactive material capable of forming a crosslinked structure by irradiation with light or thermal energy; and a transparent protective film having transparency capable of transmitting light, particularly visible light.
[0337] The hard coating layer may be formed by curing a hard coating composition comprising a photocurable (meth)acrylate monomer or oligomer and a photocurable epoxy monomer or oligomer. The photocurable (meth)acrylate monomer may comprise one or more selected from epoxy (meth)acrylate, urethane (meth)acrylate and polyester (meth)acrylate. The epoxy (meth)acrylate may be obtained by reacting a carboxylic acid having a (meth)acryloyl group with an epoxy compound.
[0338] The hard coating composition may further include one or more selected from a solvent, a photoinitiator and an additive. The additive may include one or more selected from inorganic nanoparticles, a leveling agent and a stabilizer, and in addition, may further include various components commonly used in the technical field, such as antioxidants, UV absorbers, surfactants, lubricants, antifouling agents, etc.
[0339] The transparent protective film preferably has a transmittance of 88% or more for light having a wavelength of 380 to 780 nm. For example, the transparent protective film may be the same as the transparent protective film previously exemplified as a resin substrate that can be used to manufacture a vertical polarizing film.
[0340] The thickness of the hard coating layer and the transparent protective film is preferably 5 μm or less, more preferably 4 μm or less. If the thickness of the hard coating layer and the transparent protective film is below the above upper limit, the thinning of the laminate can be achieved while fully protecting the surfaces of the first phase element, the vertical polarizing film, the polarizer, the second phase element, etc. It should be noted that the thickness of the hard coating layer and the transparent protective film is usually 1 μm or more.
[0341] The protective layer can be laminated on the first phase element, the vertical polarization film, the polarizing plate, the second phase element, etc. through a tackiness adhesive. As the tackiness adhesive that can be used, the tackiness adhesives exemplified above can be used in the same manner.
[0342] <Organic EL Display Device>
[0343] The laminated body of the present invention can be used in various display devices.
[0344] A display device refers to a device having a display element, including a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (such as field emission display devices (FED), surface field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements, plasma display devices, projection display devices (such as grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)) and piezoelectric ceramic displays. Liquid crystal display devices also include transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, Any of a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices may be display devices that display two-dimensional images, or may be stereoscopic display devices that display three-dimensional images. In particular, with respect to the laminate of the present invention, from the aspect of being easy to significantly exert its effect, it can be suitable for use in an organic electroluminescent (EL) display device, and the laminate of the present invention can be suitable for use in a liquid crystal display device and a touch panel display device. These display devices suppress unevenness when viewed from an oblique direction through polarized sunglasses when displayed in white. In addition, the coloring of internal reflected light when displayed in black can also be suppressed.
[0345] Example
[0346] Hereinafter, the present invention will be described in more detail with reference to Examples. It should be noted that "%" and "parts" in the examples refer to mass % and mass parts, respectively, unless otherwise specified.
[0347] <Example 1>
[0348] 1. Fabrication of the first phase element (HC-COP film 1) with hard coating layer 1 (HC layer 1)
[0349] A hard-coated cyclic olefin resin film (HC-COP film 1) was prepared in which an acrylic hard coating layer 1 (HC layer 1) (3 μm thick) was formed on one side of a cyclic olefin polymer (COP) film ("ZD 12" manufactured by ZEON Corporation of Japan, thickness 22 μm) (COP film 1). The pencil hardness of the surface on the HC layer 1 side of the HC-COP film 1 was 5B. The layer structure of the HC-COP film 1 was HC layer 1 / COP film 1 (ZD12).
[0350] The in-plane retardation value of the HC-COP film 1 was measured using "KOBRA-WR" manufactured by Oji Scientific Instruments Co., Ltd. The result was:
[0351] The in-plane phase difference Re(450) at a wavelength of 450nm is 105nm.
[0352] The in-plane phase difference Re(550) at a wavelength of 550nm is 100nm.
[0353] The in-plane phase difference value Re(650) at a wavelength of 650 nm is 96 nm.
[0354] 2. Preparation of UV-curable adhesive composition 1
[0355] After the cationic curable components a1 to a3 shown below and the cationic polymerization initiator are mixed in the following amounts, the cationic polymerization initiator and the sensitizer shown below are added in the following amounts, further mixed, and the obtained mixture is degassed to prepare an ultraviolet curable adhesive composition 1. It should be noted that in the following amounts, the amount of the cationic polymerization initiator (OXT-221) is the amount of the solid content.
[0356] Cationic curable component a1 (32.5 parts by mass): 3',4'-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate ("CEL2021P" manufactured by Daicel)
[0357] Cationic curable component a2 (7.5 parts by mass): an epoxy compound containing an alicyclic structure ("EHPE3150" manufactured by Daicel)
[0358] Cationic curable component a3 (60 parts by mass): 3,3′-(oxybismethylene)bis(3-ethyloxetane) (Toagosei Co., Ltd., “OXT-221”)
[0359] Cationic polymerization initiator (2.25 parts by mass): "CPI-100" manufactured by San-Apro (propylene carbonate solution having a solid content of 50% by mass)
[0360] Sensitizer (2 parts by mass): 1,4-diethoxynaphthalene
[0361] 3. Preparation of Composition for Forming Hard Coat Layer 2 (HC Layer 2)
[0362] The components shown below were mixed in the following blending amounts, and stirred at 80° C. for 1 hour to prepare a composition for forming the hard coat layer 2 (HC layer 2 ).
[0363] Acrylate compound (50 parts by mass): dipentaerythritol hexaacrylate
[0364] Urethane acrylate compound (50 parts by mass): Urethane acrylate ("EBECRYL 4858" manufactured by DAICEL-ALLNEX)
[0365] Radical polymerization initiator (3 parts by mass): 2-[4-(methylthio)benzoyl]-2-(4-morpholinyl)propane ("Irgacure 907" manufactured by BASF)
[0366] Solvent (10 parts by mass): methyl ethyl ketone
[0367] 4. Preparation of release film with HC layer 2
[0368] A polyethylene terephthalate (PET) film (MRV38 (V04) manufactured by Mitsubishi Chemical Co., Ltd.) (release film) having a release treatment applied to its release-treated surface was subjected to corona treatment, and the composition for forming the HC layer 2 obtained above was applied by a bar coating method (#230 mm / sec) to form a coating film. The film was then exposed to light (accumulated light intensity at a wavelength of 365 nm) at a dose of 500 mJ / cm using a UV irradiation device (SPOT CURESP-7 manufactured by USHIO ELECTRIC CO., LTD.). 2 The coating film was irradiated with ultraviolet rays in a manner to obtain a release film with an HC layer having an HC layer 2 formed on the surface of the release film. The thickness of the HC layer 2 was measured by a contact film thickness meter, and the result was 2 μm. The layer structure of the release film with the HC layer 2 was HC layer 2 / PET film (MRV38 (V04)).
[0369] 5. Preparation of a composition for forming a vertical polarizing film MC
[0370] The polymerizable liquid crystal compounds 1 and 2, dichroic dyes 1 and 2, polymerization initiators, leveling agents, and solvents shown below were mixed in the amounts shown below, respectively, and stirred at 80° C. for 1 hour to obtain a composition for forming a perpendicular polarizing film MC.
[0371] Each dichroic dye is an azo dye described in the examples of JP-A-2013-101328. Polymerizable liquid crystal compounds 1 and 2 were synthesized according to the method described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).
[0372] Polymerizable liquid crystal compound 1 (75 parts by mass):
[0373] [Chemical formula 9]
[0374]
[0375] Polymerizable liquid crystal compound 2 (25 parts by mass):
[0376] [Chemical formula 10]
[0377]
[0378] Dichroic dye 1 (Magenta dye) (2.8 parts by mass):
[0379] [Chemical formula 11]
[0380]
[0381] Absorption maximum wavelength of dichroic pigment 1: 526nm
[0382] Dichroic pigment 2 (cyan pigment) (2.8 parts by mass):
[0383] [Chemical formula 12]
[0384]
[0385] Absorption maximum wavelength of dichroic pigment 2: 600nm
[0386] Polymerization initiator (6 parts by mass): 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure 369" manufactured by Ciba Specialty Chemicals)
[0387] Leveling agent (0.3 parts by mass): polyacrylate compound (BYK-361N manufactured by BYK-Chemie)
[0388] Solvent (250 parts by mass): o-xylene
[0389] 6. Preparation of composition for forming alignment layer 4
[0390] The aligning polymer shown below was prepared in the following blending amount, and propylene glycol monomethyl ether was added thereto in the following blending amount to obtain a composition for forming an alignment layer 4 .
[0391] Orienting polymer (0.3 parts by mass): "SUNEVER (registered trademark) SE-610" manufactured by Nissan Chemical Industries, Ltd. (in the form of a solution, solid content concentration: 1.0% by mass)
[0392] Propylene glycol monomethyl ether (27.7 parts by mass)
[0393] 7. Fabrication of vertical polarizing film MC
[0394] 7-1. Preparation of vertical polarizing film MC
[0395] The composition for forming an orientation layer 4 obtained in 6. was applied onto the HC layer 2 of the release film with HC layer 2 (HC layer 2 / PET film (MRV38 (V04)) obtained in 4. above using a rod coater, and dried in a drying oven set at 120°C for 1 minute to form an orientation layer 4. On the obtained orientation layer 4, the composition for forming a vertical polarizing film MC obtained in 5. was applied onto the obtained orientation layer 4 using a rod coater, and heated at 100°C for 60 seconds to obtain a dry coating film, which was naturally cooled to room temperature and illuminated in a nitrogen atmosphere using a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) at a cumulative light intensity of 1000 mJ / cm at a wavelength of 365 nm. 2 UV rays were irradiated from the dried coating film side to obtain a vertical polarizing plate MC comprising PET film (MRV38 (V04)) / HC layer 2 / orientation layer 4 / vertical polarizing film MC. The thickness of the vertical polarizing film MC including the orientation layer measured by a contact film thickness meter was 2 μm.
[0396] 7-2. Absorbance measurement of vertical polarization film MC
[0397] The liquid crystal coated surface of the prepared vertical polarizing plate MC was bonded to a 4×4 cm×0.7 mm thick glass via a 25 μm pressure-sensitive adhesive (manufactured by LINTEC). After the PET film was peeled off, the glass was placed in an ultraviolet-visible spectrophotometer (“UV-2450” manufactured by Shimadzu Corporation) to measure the absorbance at an elevation angle of 40°. In addition, the absorption maximum wavelength (λ max ), AxC and AxC(z=60).
[0398] It should be noted that the x-axis refers to any direction within the plane of the vertical polarizing film, the y-axis refers to the direction perpendicular to the x-axis within the film plane, and the z-axis refers to the thickness direction of the vertical polarizing film. AxC and AxC(z=60) are both the absorbance of the above-mentioned vertical polarizing film at the absorption maximum wavelength of 400-750nm. AxC represents the absorbance of linear polarized light vibrating in the x-axis direction, and AxC(z=60) represents the absorbance of linear polarized light vibrating in the x-axis direction when the above-mentioned film is rotated 60° with the y-axis as the rotation axis.
[0399] In addition, when measuring the absorbance, the sample was placed in an ultraviolet visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation), and after calibration was performed so that the absorbance at 800nm became zero, AxC was measured. For AxC (z = 60), the sample was similarly placed and tilted, and after calibration was performed so that the absorbance at 800nm became zero, AxC (z = 60) was measured. The AxC of the vertical polarizing film MC at 530nm was 0.115, AxC (z = 60) was 0.692, and the AxC at 606nm was 0.062, and AxC (z = 60) was 0.639. In addition, the absorption maximum wavelength (λ) in the tilt direction max ) are 526nm and 606nm.
[0400] 8. Preparation of polarizing plate 5
[0401] 8-1. Preparation of polarizing film
[0402] A polyvinyl alcohol resin film with a thickness of 20 μm (average degree of polymerization of about 2400, degree of saponification of 99.9 mol% or more) was longitudinally uniaxially stretched to about 5 times by dry stretching, and then immersed in pure water at a temperature of 60°C for 1 minute while maintaining the tension, and then immersed in an aqueous solution at a temperature of 28°C with a mass ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 for 60 seconds. Then, it was immersed in an aqueous solution at a temperature of 72°C with a mass ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 for 300 seconds. Subsequently, after washing with pure water at a temperature of 26°C for 20 seconds, it was dried at a temperature of 65°C to obtain a polarizing film with a thickness of 8 μm in which iodine was adsorbed and oriented on the polyvinyl alcohol resin film.
[0403] 8-2. Preparation of water-based adhesive
[0404] 3 parts by mass of carboxyl-modified polyvinyl alcohol ("KL-318" manufactured by Kuraray Co., Ltd.) was dissolved in 100 parts by mass of water to prepare a polyvinyl alcohol aqueous solution. A water-soluble polyamide epoxy resin ("Sumirez Resin 650 (30)" manufactured by Taoka Chemical Industry Co., Ltd., solid content concentration 30% by mass) was mixed in the obtained aqueous solution in an amount of 1.5 parts by mass relative to 100 parts by mass of water in the aqueous solution to obtain a water-based adhesive.
[0405] 8-3. Preparation of polarizing plate
[0406] A HC cyclic olefin resin film (HC-COP film 2) having an acrylic hard coating layer 3 (HC layer 3) (thickness 3 μm) formed on one side of a cyclic olefin polymer (COP) film ("ZF" manufactured by ZEON Corporation, Japan) (thickness 13 μm) was prepared. The pencil hardness of the surface of the HC layer 3 side of the HC-COP film 2 was 5B. The COP film side (the side opposite to the HC layer 3 side) of the HC-COP film 2 was bonded to one side of the polarizing film obtained in 8-1. above by means of the water-based adhesive prepared in 8-2. above, and a laminate A (polarizing plate) having a layer structure of HC-COP film 2 / water-based adhesive / polarizing film was obtained. The in-plane retardation Re(550) of the HC-COP film 2 at a wavelength of 550 nm was 0 (zero) nm, and the total light transmittance Ht (%) was measured using an integrating sphere light transmittance measuring device ("Haze Meter Hz-5 V3" manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K7105 and was 92.6%.
[0407] 9. Fabrication of multiple phase difference plates
[0408] 9-1. Preparation of composition for forming alignment layer D
[0409] The alignment material represented by the following chemical formula (weight average molecular weight: 50000, m:n=50:50) was prepared according to the method described in Japanese Patent Application Laid-Open No. 2021-196514. 2 parts by mass of the alignment material was mixed with 98 parts by mass of cyclopentanone (solvent), and the resulting mixture was stirred at 80° C. for 1 hour to prepare an alignment layer D-forming composition.
[0410] Oriented materials:
[0411] [Chemical formula 13]
[0412]
[0413] 9-2. Preparation of polymerizable liquid crystal compounds
[0414] The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) represented by the following chemical formula were prepared respectively. The polymerizable liquid crystal compound (A1) was prepared in the same manner as described in Japanese Patent Application Laid-Open No. 2019-003177. The polymerizable liquid crystal compound (A2) was prepared in the same manner as described in Japanese Patent Application Laid-Open No. 2009-173893.
[0415] Polymerizable liquid crystal compound (A1):
[0416] [Chemical formula 14]
[0417]
[0418] Polymerizable liquid crystal compound (B1):
[0419] [Chemical formula 15]
[0420]
[0421] 1 mg of polymerizable liquid crystal compound (A1) was dissolved in 10 mL of chloroform to obtain a solution. The obtained solution was added to a measuring cuvette with an optical path length of 1 cm, and the measuring sample was placed in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) as a measuring sample to measure the absorption spectrum. The wavelength at which the maximum absorbance is reached was read from the obtained absorption spectrum, and the maximum absorption wavelength λ in the range of 300 to 400 nm was max It is 356nm.
[0422] 9-3. Preparation of Composition for Forming Phase Difference Film 6
[0423] The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 mass parts of a leveling agent ("BYK-361N" manufactured by BM Chemie) and 3 mass parts of a photopolymerization initiator ("Irgacure OXE-03" manufactured by BASF Japan) were added to 100 mass parts of the obtained mixture. In addition, N-methyl-2-pyrrolidone (NMP) was added in such a manner that the solid content concentration became 13 mass%. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a composition for forming a phase difference film 6.
[0424] 9-4. Preparation of Adhesive Sheet 1
[0425] 9-4. (1) Preparation of Adhesive Composition 1
[0426] A mixed solution of 100 parts of ethyl acetate, 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate and 0.5 parts of acrylic acid was placed in a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirrer, and the internal temperature was raised to 55°C while replacing the air in the device with nitrogen to make it oxygen-free. Then, the entire amount of a solution prepared by dissolving 0.12 parts of azobisisobutyronitrile (polymerization initiator) in 10 parts of ethyl acetate was added. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hour while the internal temperature was maintained at 54-56°C. The addition of ethyl acetate was stopped at the time when the concentration of the (meth)acrylic resin reached 35% by mass, and the temperature was further maintained at the same temperature until 6 hours had passed since the addition of ethyl acetate was started. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, thereby preparing an acrylic resin solution 2. The weight average molecular weight Mw of the obtained acrylic resin was 1.7 million, and the molecular weight distribution Mw / Mn was 3.9. It should be noted that Mw and Mn were measured as follows: two "TSKgelGMHHR-H(S)" manufactured by Tosoh Corporation were connected in series in a GPC device as columns, tetrahydrofuran was used as an eluent, and the sample concentration was 2 mg / mL, the sample introduction amount was 100 μL, the temperature was 40°C, and the flow rate was 1 mL / min, and the measurement was performed by standard polystyrene conversion.
[0427] To 80 parts by mass of the solid content of the acrylic resin solution 1 obtained above, 20 parts by mass (solid content) of a difunctional acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts by mass of a crosslinking agent ("Coronate L" manufactured by Tosoh Corporation (an ethyl acetate solution of a trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75% by mass)) in an effective amount, 1.5 parts by mass of a photopolymerization initiator ("Irgacure 500" manufactured by Ciba Specialty Chemicals), and 0.3 parts by mass of a silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and ethyl acetate was further added so that the solid content concentration became 13%, thereby obtaining an adhesive composition 1.
[0428] The difunctional acrylate (A-DOG) is a diacrylate of an acetal compound of hydroxypivaldehyde and trimethylolpropane, and has the following structure.
[0429] [Chemical formula 16]
[0430]
[0431] 9-4. (2) Preparation of Adhesive Sheet 1
[0432] Using an applicator, the above-prepared adhesive composition 1 was applied to the release-treated surface of a separator [MRV38 (V04) manufactured by Mitsubishi Chemical Corporation], which is a polyethylene terephthalate film with a single-sided release treatment, so that the thickness after drying became 15 μm, and dried at 100 °C for 1 minute to form an adhesive layer 1. Then, the release-treated surface of a separator [MRF38 manufactured by Mitsubishi Chemical Corporation], which is a polyethylene terephthalate film with a single-sided release treatment, was adhered to the surface of the formed adhesive layer 1 on the side opposite to the separator. Then, ultraviolet rays were irradiated under the following conditions to produce an adhesive sheet 1. The layer structure of this adhesive sheet 1 is separator (MRV38 (V04)) / adhesive layer 1 / separator (MRF38).
[0433] <UV Irradiation Conditions>
[0434] ·Fusion UV lamp system (manufactured by Fusion UV Systems, using H lamp)
[0435] ·Cumulative light amount 250 mJ / cm 2
[0436] Production of Horizontally Oriented Retardation Film (Z1)
[0437] On a biaxially stretched polyethylene terephthalate (PET) film (DIAFOIL manufactured by Mitsubishi Rayon Co., Ltd.) as substrate C, the composition for forming the alignment layer D obtained above was applied by a bar coater to obtain a coated film. After the obtained coated film was dried at 120 °C for 2 minutes, it was cooled to room temperature to form a dried film. Then, using a UV irradiation device (SPOT CURE SP-9 manufactured by USHIO Inc.), polarized ultraviolet light was irradiated to this dried film so that the cumulative light amount at a wavelength of 313 nm became 100 mJ / cm 2 to obtain an alignment layer D. The thickness of this alignment layer D was measured using an ellipsometer (M-220 manufactured by Nippon Bunko Co., Ltd.), and the result was 100 nm.
[0438] On the obtained alignment layer D, the composition for forming the retardation film 6 obtained above was applied by a bar coater to form a coated film. After this coated film was heated and dried at 120 °C for 2 minutes, it was cooled to room temperature to obtain a dried film. Next, using a high-pressure mercury lamp (Unicure VB-15201BY-A manufactured by USHIO Inc.), in a nitrogen atmosphere, the cumulative light amount (exposure amount) at 365 nm was made to be 500 mJ / cm 2The dried film is irradiated with ultraviolet light in a manner to form a horizontally oriented phase difference film (horizontally oriented liquid crystal cured film) 6 on the orientation layer D, thereby obtaining a horizontally oriented phase difference film (Z1). The horizontally oriented phase difference film 6 constituting the horizontally oriented phase difference film (Z1) is a phase difference film formed by curing a polymerizable liquid crystal compound in a state of being oriented in a horizontal direction in a plane relative to the substrate C. The layer structure of the horizontally oriented phase difference film (Z 1) is substrate C / orientation layer D / horizontally oriented phase difference film 6. The film thickness of the horizontally oriented phase difference film 6 measured using a laser microscope ("LEXT OLS4100" manufactured by Olympus Corporation) is 2.0 μm.
[0439] The surface of the horizontally oriented phase difference film 6 side of the horizontally oriented phase difference film (Z 1) obtained above is subjected to corona treatment, and the adhesive layer 1 of the diaphragm peeled off from the above-mentioned adhesive sheet 1 is bonded to the glass plate, and the substrate C is peeled off and removed to obtain a measurement sample with the structure of the oriented layer D / horizontally oriented phase difference film 6 / adhesive layer 1 / glass plate. The in-plane phase difference value of the measurement sample was measured using a phase difference measuring device ("KOBRA-WR" manufactured by Prince Instruments Co., Ltd.). It should be noted that the in-plane phase difference value for light with wavelengths of 450nm, 550nm and 650nm is obtained by the Cauchy dispersion formula based on the measurement results of the in-plane phase difference for light with wavelengths of 448.2nm, 498.6nm, 548.4nm, 587.3nm, 628.7nm and 748.6nm. The in-plane phase difference Re(450) at a wavelength of 450 nm is 122 nm, the in-plane phase difference Re(550) at a wavelength of 550 nm is 140 nm, and the in-plane phase difference Re(650) at a wavelength of 650 nm is 144 nm. The relationship between the in-plane phase differences at each wavelength is as follows.
[0440] Re(450) / Re(550)=0.87
[0441] Re(650) / Re(550)=1.03
[0442] [Wherein, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650 nm.]
[0443] 9-6. Preparation of Composition for Forming Phase Difference Film 7
[0444] 100 parts by mass of a polymerizable liquid crystal compound ("Paliocolor LC242" sold by BASF Japan), 0.1 parts by mass of a leveling agent ("BYK-361N" manufactured by BYK-Chemie), and 2.5 parts by mass of a photopolymerization initiator ("Omnirad907" manufactured by IGM Resin BV) were mixed, 400 parts by mass of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the mixture was stirred at a temperature of 80°C for 1 hour to prepare a composition for forming a phase difference film 7.
[0445] The polymerizable liquid crystal compound "Paliocolor LC242" is a compound represented by the following chemical formula.
[0446] [Chemical formula 17]
[0447]
[0448] 9-7. Preparation of Oriented Polymer Composition
[0449] 2-Butoxyethanol was added to an oriented polymer ("SUNEVERSE-610" manufactured by Nissan Chemical Industries, Ltd.) so that the solid content concentration became 1% by mass, thereby obtaining an oriented polymer composition.
[0450] 9-8. Preparation of vertically oriented phase difference film (Z2)
[0451] A corona treatment device ("AGF-B 1 0" manufactured by Kasuga Electric Co., Ltd.) was used to apply corona treatment to one side of a cycloolefin polymer (COP) film ("ZF" manufactured by ZEON Corporation of Japan) (COP film ZF). Subsequently, the above-obtained oriented polymer composition was applied to the surface subjected to the corona treatment using a rod coater, and dried at 90°C for 1 minute to obtain an oriented layer 8. The film thickness of the obtained oriented layer 8 was measured using a laser microscope, and the result was 30 nm. The above-obtained composition for forming a phase difference film 7 was applied to the obtained oriented layer 8 using a rod coater, and dried at 90°C for 1 minute to form a dry film. A high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) was used, and the accumulated light amount (exposure amount) at 365 nm in a nitrogen atmosphere was 1000 mJ / cm 2The dried film is irradiated with ultraviolet light in a manner to form a vertically oriented phase difference film (vertically oriented liquid crystal cured film) 7, thereby obtaining a vertically oriented phase difference film (Z2). The layer structure of the vertically oriented phase difference film (Z2) is COP film ZF / orientation layer 8 / vertically oriented phase difference film 7. The film thickness of the formed vertically oriented phase difference film 7 was measured using a laser microscope, and the result was 450nm. The in-plane phase difference of the vertically oriented phase difference film (Z2) was measured using a phase difference measuring device ("KOBRA-WR" manufactured by Prince Instruments Co., Ltd.). As a result, the in-plane phase difference Re(550) at a wavelength of 550nm is 1nm, and the phase difference Rth(550) in the thickness direction at a wavelength of 550nm is -70nm. This indicates the optical properties shown in the following formula (3). It should be noted that the phase difference of the COP film ZF used at a wavelength of 550nm is approximately 0. In addition, the in-plane phase difference of the orientation layer 8 constituting the vertically oriented phase difference film (Z2) at a wavelength of 550nm is also approximately 0. Therefore, the measured Re (550) and Rth (550) are the optical properties of the vertically oriented phase difference film 7 constituting the vertically oriented phase difference film (Z2).
[0452] nx≈ny<nz (3)
[0453] [nx is the refractive index in the slow axis direction in the plane, ny is the refractive index in the fast axis direction in the plane (direction perpendicular to the slow axis direction), and nz is the refractive index in the thickness direction.]
[0454] 9-9. Preparation of UV-curable adhesive composition 9
[0455] After mixing the cationic curable components a1 to a3 and the cationic polymerization initiator shown below in the following blending amounts, the cationic polymerization initiator and the sensitizer shown below were further mixed in the following blending amounts, and the obtained mixture was degassed to prepare an ultraviolet curable adhesive composition 9.
[0456] Cationic curable component a1 (70 parts by mass): 3',4'-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate ("CEL2021P" manufactured by Daicel)
[0457] Cationic curable component a2 (20 parts by mass): neopentyl glycol diglycidyl ether ("EX-211" manufactured by Nagase ChemteX)
[0458] Cationic curable component a3 (10 parts by mass): 2-ethylhexyl glycidyl ether ("EX-121" manufactured by Nagase ChemteX)
[0459] Cationic polymerization initiator (2.25 parts by mass (solid content): "CPI-100" manufactured by San-Apro, a solution of 50% by mass of solid content and 50% by mass of propylene carbonate)
[0460] Sensitizer (2 parts by mass): 1,4-diethoxynaphthalene
[0461] In addition, the compounding amount (2.25 mass parts) of the cationic polymerization initiator (CPI-100) is the compounding amount converted into solid content.
[0462] 9-10. Fabrication of multiple phase difference plates
[0463] The horizontally oriented retardation film (Z1) (substrate C / orientation layer D / horizontally oriented retardation film 6) obtained above, and the vertically oriented retardation film (Z2) (COP film ZF / orientation layer 8 / vertically oriented retardation film 7) obtained above The side of the film is subjected to corona treatment, and the adhesive layer 9 (thickness 2μm) formed by the ultraviolet curable adhesive composition 9 prepared above is used for bonding. From the side of the vertically oriented retardation film (Z2), an ultraviolet irradiation device with a conveyor belt (the lamp used is the "H bulb" manufactured by Fusion UV Systems Co., Ltd.) is used to irradiate with an intensity of 390W / cm in the UVA region (wavelength 320nm~390nm). 2 , the accumulated light intensity is 420mJ / cm 2 The irradiation intensity is 400mW / cm in the U VB region (wavelength 280nm~320nm). 2 , the accumulated light intensity is 400mJ / cm 2 The ultraviolet curing adhesive composition was cured by irradiating ultraviolet rays in a manner to form an adhesive layer 9, thereby obtaining a laminate B. The layer structure of the laminate B is substrate C / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. The in-plane phase difference of the laminate B at a wavelength of 550 nm is 140 nm.
[0464] (1) Preparation of optical laminate
[0465] After the substrate C (PET film) in the laminate B [substrate C / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF] obtained in the above 9-10. is peeled off to expose the orientation layer D, the exposed orientation layer D is subjected to a corona treatment. On the other hand, the separator (MRF38) of the adhesive sheet 1 obtained in the above 9-4. is peeled off to expose the adhesive layer 1, and the exposed surface of the exposed adhesive layer 1 is attached to the orientation layer D subjected to the above corona treatment, thereby obtaining a laminate having a layer structure of separator (MRV38 (V04)) / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. Another separator (MRV38 (V04)) was peeled off from the laminate to expose the adhesive layer 1, and the laminate A (HC-COP film 2 / water-based adhesive / polarizing film) was bonded on the exposed adhesive layer 1 on its polarizing film side to produce a laminate C. The layer structure of the laminate C is HC-COP film 2 / water-based adhesive / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF.
[0466] (2) Preparation of optical laminate (intermediate) (Preparation of laminate D)
[0467] The COP film 1 side surface of the HC-COP film 1 obtained in 1. above and the surface of the vertical polarizing film MC obtained in 7. above were subjected to corona treatment, respectively, and laminated with the layer (thickness 2 μm) of the ultraviolet curing adhesive 1 composition prepared in the above “Preparation of ultraviolet curing adhesive 1 composition”, and from the vertical polarizing film MC side, an ultraviolet irradiation device with a conveyor belt (the lamp used was an “H bulb” manufactured by Fusion UV Systems) was used to irradiate with an intensity of 390 W / cm in the UVA region (wavelength 320 nm to 390 nm). 2 , the accumulated light intensity is 420mJ / cm 2 The irradiation intensity in the UVB region (wavelength 280nm to 320nm) is 400mW / cm 2 , the accumulated light intensity is 400mJ / cm 2 The ultraviolet rays were irradiated in a manner to cure the ultraviolet curing adhesive composition 1 to form an adhesive layer, thereby obtaining a laminate D. The layer structure of the laminate D is HC layer 1 / COP film 1 (ZD1 2) / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / PET film (MRV38 (V04)).
[0468] The PET film (MRV38 (V04)) was peeled off from the laminate D obtained in (2) above to expose the HC layer 2, and the surface of the exposed HC layer 2 was subjected to a corona treatment. The separator (MRF38) was peeled off from the adhesive sheet 1 (adhesive layer 5 μm) obtained above to expose the adhesive layer 1, and the adhesive layer 1 was bonded to the HC layer 2 subjected to the corona treatment, and the separator (MRV38 (V04)) was peeled off to expose the adhesive layer 1, thereby obtaining a laminate E. The laminate E had a layer structure of HC layer 1 / COP film 1 (ZD12) / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1.
[0469] The surface of the HC-COP film 2 side of the stack C was subjected to corona treatment and bonded to the exposed adhesive layer 1 of the stack E to produce an optical stack MC1. The layer structure of the optical stack MC1 is HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. In addition, the stacking was performed in such a way that the angle (θ) formed by the slow axis of the COP film 1 and the absorption axis of the polarizing film was 45°.
[0470] In the optical laminate MC1, the COP film 1 corresponds to the first phase element, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned phase difference film 6 corresponds to the second phase element.
[0471] <Example 2>
[0472] An optical laminate MC2 was prepared in the same manner as in Example 1 except that a uniaxially stretched cycloolefin polymer (COP) film ("ZT" manufactured by ZEON Corporation of Japan) (COP film 2) (thickness: 21 μm) was used instead of the HC-COP film 1. The layer structure of the optical laminate MC2 is COP film 2 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 3 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. In the optical laminate MC2, the COP film 2 is equivalent to the first phase element, the vertical polarizing film MC / orientation layer 4 is equivalent to the vertical polarizing film, and the orientation layer D / horizontally oriented phase difference film 6 is equivalent to the second phase element.
[0473] The in-plane phase difference value of the COP film uniaxially stretched in the width direction used here was measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. The result was:
[0474] The in-plane phase difference at a wavelength of 450nm is Re(450)=134nm.
[0475] The in-plane phase difference at a wavelength of 550nm is Re(550)=132nm.
[0476] The in-plane phase difference value at a wavelength of 650 nm is Re(650)=131 nm.
[0477] <Example 3>
[0478] A multilayer body MC3 was produced in the same manner as in Example 1 except that the retardation film Q produced below was used instead of the HC-COP film 1 .
[0479] [Preparation of Oriented Polymer Composition 9]
[0480] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 completely saponified type, manufactured by Wako Pure Chemical Industries, Ltd.), and the mixture was heated at 100° C. for 1 hour, thereby obtaining an oriented polymer composition 9.
[0481] [Preparation of Composition for Forming Phase Difference Film Q1]
[0482] 100 parts by mass of a polymerizable liquid crystal compound "Paliocolor LC242" (manufactured by BASF Japan), 0.1 parts by mass of a leveling agent "BYK-361N" (manufactured by BYK-Chemie), and 2.5 parts by mass of "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added. In addition, 400 parts by mass of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the mixture was stirred at a temperature of 80° C. for 1 hour to prepare a composition for forming a phase difference film Q1.
[0483] Polymerizable liquid crystal compound LC242:
[0484] [Chemical formula 18]
[0485]
[0486] [Production of Phase Difference Film Q]
[0487] An oriented polymer composition 9 was coated on a triacetate cellulose film (TAC) (manufactured by Konica Minolta Co., Ltd., KC4UY) cut into a rectangular shape, and after heating and drying, an oriented polymer film (oriented layer 9) with a thickness of 100 nm was formed. The surface of the obtained oriented polymer film was subjected to a friction treatment at an angle of 15° to the long side direction of the above-mentioned TAC, and a phase difference film Q1 forming composition was coated thereon using a rod coater. The obtained coated film was dried at 100°C for 1 minute and then cooled to room temperature to obtain a dry film. Next, a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) was used to irradiate the above-mentioned dry film with an exposure amount of 1000mJ / cm 2 (365nm benchmark) ultraviolet light, thereby forming a phase difference film Q1 in which the polymerizable liquid crystal compound is oriented in the horizontal direction relative to the substrate surface and solidified, and a phase difference film Q comprising TAC / orientation layer 9 / phase difference film Q1 (horizontally oriented liquid crystal solidified film) is obtained. The film thickness of the obtained phase difference film Q1 was measured using a laser microscope, and the result was 1.0μm. The in-plane phase difference value was measured using KOBRA-WR manufactured by Prince Instruments Co., Ltd. The result is,
[0488] The in-plane phase difference at a wavelength of 450nm is Re(450)=127nm.
[0489] The in-plane phase difference at a wavelength of 550nm is Re(550)=115nm.
[0490] The in-plane phase difference value at a wavelength of 650 nm is Re(650)=111 nm.
[0491] It should be noted that the phase difference value of TAC at a wavelength of 550 nm is approximately 0, and therefore has no influence on the optical properties. The orientation angle is 15° with respect to the long side direction of the TAC.
[0492] The laminate DQ was obtained by using the phase difference film Q obtained above instead of the HC-COP film 1 and performing corona treatment on the phase difference film Q1 side of the phase difference film Q. The layer structure of the laminate DQ was TAC / orientation layer 9 / phase difference film Q1 / adhesive layer 1 / vertical orientation film MC / orientation layer 4 / HC layer 2 / PET film (MRC38 (V04)).
[0493] The layer structure of the optical laminate MC3 is TAC / orientation layer 9 / phase difference film Q1 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. In the optical laminate MC3, the orientation layer 9 / phase difference film Q1 is equivalent to the first phase element, the vertical polarizing film MC / orientation layer 4 is equivalent to the vertical polarizing film, and the orientation layer D / horizontally oriented phase difference film 6 is equivalent to the second phase element.
[0494] <Example 4>
[0495] A laminate DZ1 was obtained in the same manner as the laminate D except that a horizontally oriented phase difference film Z1 was used instead of the HC-COP film 1 and the corona treatment was applied to the horizontally oriented phase difference film side of the horizontally oriented phase difference film Z1. The laminate DZ1 had a layer structure of substrate C / orientation layer D / horizontally oriented phase difference film 6 (horizontally oriented liquid crystal cured film) / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / PET film (MRV38 (V04)).
[0496] Optical laminate MC4 was produced in the same manner as in Example 1 except that laminate DZ1 was used instead of laminate D. When laminate DZ1 was produced, the liquid crystal film of the horizontal alignment retardation film ( Z1 ) and the vertical polarizing film MC were bonded together via the adhesive layer 1 .
[0497] The layer structure of the optical laminate MC4 is substrate C / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertical oriented phase difference film 7 / orientation layer 8 / COP film ZF. In the optical laminate MC4, the orientation layer D / horizontally oriented phase difference film 6 is equivalent to the first phase element, the vertical polarizing film MC / orientation layer 4 is equivalent to the vertical polarizing film, and the orientation layer D / horizontally oriented phase difference film 6 is equivalent to the second phase element.
[0498] <Example 5>
[0499] In the preparation of the composition for forming the vertical polarizing film MC in 7. above, 2.8 parts by mass of the following dichroic pigment 3 (yellow pigment) was used instead of the dichroic pigments 1 to 2. In addition, the same operation as the preparation of the composition for forming the vertical polarizing film MC was performed to obtain a composition for forming the vertical polarizing film Y containing the dichroic pigment 3. The same operation as the preparation of the vertical polarizing film MC was performed to obtain the vertical polarizing film Y. The AxC of the vertical polarizing film Y was 0.049, the AxC (z = 60) was 0.468, and the absorption maximum wavelength (λ) in the oblique direction was 0.049. max ) was 402 nm. An optical laminate Y1 was obtained in the same manner as in Example 1 except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0500] Dichroic pigment 3 (yellow pigment) (2.8 parts by mass):
[0501] [Chemical formula 19]
[0502]
[0503] Absorption maximum wavelength of dichroic pigment 3: 400nm
[0504] <Example 6>
[0505] An optical layered body Y2 was obtained in the same manner as in Example 2 except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0506] <Example 7>
[0507] An optical laminate Y3 was obtained in the same manner as in Example 3 except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0508] <Example 8>
[0509] An optical layered body Y4 was obtained in the same manner as in Example 4 except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0510] <Example 9>
[0511] In the preparation of the composition for forming the vertical polarizing film MC in the above 7., 2.8 parts by mass of dichroic dye 1 (magenta pigment) and 2.8 parts by mass of dichroic dye 3 (yellow pigment) used in Example 5 were used instead of dichroic dyes 1 to 2. Otherwise, the same operation as the preparation of the composition for forming the vertical polarizing film MC was performed to obtain a composition for forming a vertical polarizing film YM containing dichroic dye 1 and dichroic dye 3. The same operation as the preparation of the vertical polarizing film MC was performed to obtain the vertical polarizing film YM. The AxC of the vertical polarizing film YM at 390nm is 0.049, and the AxC (z=60) is 0.468. In addition, the AxC at 530nm is 0.115, and the AxC (z=60) is 0.692. The absorption maximum wavelength (λ max ) were 402 nm and 526 nm. An optical laminate YM1 was obtained in the same manner as in Example 1 except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0512] <Example 10>
[0513] An optical layered body YM2 was obtained in the same manner as in Example 2 except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0514] <Example 11>
[0515] An optical laminate YM3 was obtained in the same manner as in Example 3 except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0516] <Example 12>
[0517] An optical laminate YM4 was obtained in the same manner as in Example 4 except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0518] <Example 13>
[0519] In the preparation of the composition for forming the vertical polarizing film MC in 7. above, 2.8 parts by mass of dichroic dye 2 (cyan dye) was used instead of dichroic dyes 1 to 2. In addition, the same operation as the preparation of the composition for forming the vertical polarizing film MC was performed to obtain a composition for forming the vertical polarizing film C containing dichroic dye 2. The same operation as the preparation of the vertical polarizing film MC was performed to obtain the vertical polarizing film C. The AxC of the vertical polarizing film C was 0.062, the AxC (z = 60) was 0.639, and the absorption maximum wavelength (λ) in the oblique direction was 0.062. max ) was 606 nm. An optical laminate C1 was obtained in the same manner as in Example 1 except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0520] <Example 14>
[0521] An optical layered body C2 was obtained in the same manner as in Example 2 except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0522] <Example 15>
[0523] An optical laminate C3 was obtained in the same manner as in Example 3 except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0524] <Example 16>
[0525] Optical layered body C4 was obtained in the same manner as in Example 4 except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0526] <Example 17>
[0527] 10. Preparation of Composition for Forming Horizontal Polarizing Film
[0528] The polymerizable liquid crystal compounds 1 to 2, dichroic dyes 1 to 3, polymerization initiator, leveling agent and solvent used in the preparation of the vertical polarizing film were mixed in the following amounts and stirred at 80° C. for 1 hour to obtain a composition for forming a horizontal polarizing film.
[0529] 11. Fabrication of horizontal polarization plate
[0530] The horizontal polarizing film was prepared in the same manner as the vertical polarizing film except that the drying conditions after coating the horizontal polarizing film-forming composition were set to 120 degrees, thereby obtaining a horizontal polarizing plate comprising PET film (MRV38 (V04)) / HC layer 2 / orientation layer 4 / horizontal polarizing film.
[0531] The thickness of the horizontal polarizing film measured with a contact-type film thickness meter was 2 μm.
[0532] 12. Preparation of optical laminate MC'
[0533] The surface of the horizontal polarizing film of the horizontal polarizing plate was subjected to corona treatment and bonded to the exposed adhesive layer 1 of the laminate E obtained above to produce a laminate F. The laminate F had a layer structure of HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1 / horizontal polarizing film / orientation layer 4 / HC layer 2 / PET film (MRV38 (V04)). In addition, the laminate was performed in such a way that the angle (θ) formed by the slow axis of the COP film 1 and the absorption axis of the horizontal polarizing film was 45°.
[0534] After the substrate C (PET film) in the laminate B obtained in 9-10. is peeled off to expose the orientation layer D, the exposed orientation layer D is subjected to a corona treatment. On the other hand, the separator (MRF38) of the adhesive sheet 1 obtained in 9-4. is peeled off to expose the adhesive layer 1, and the exposed surface of the exposed adhesive layer 1 is bonded to the orientation layer D subjected to the corona treatment, thereby obtaining a laminate having a layer structure of separator (MRV38 (V04)) / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. Another separator (MRV38 (V04)) is peeled off from the laminate to expose the adhesive layer 1, and the outermost HC layer 2 to which the PET film is peeled off from the laminate F and subjected to a corona treatment is bonded to the exposed adhesive layer 1, thereby producing an optical laminate MC'1. The layer structure of the optical laminate MC'1 is HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / orientation layer 4 / HC layer 2 / adhesive layer 1 / horizontal polarizing film / orientation layer 4 / HC layer 2 / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. In addition, the layers are laminated in such a manner that the angle (θ) formed by the slow axis of the COP film 1 and the absorption axis of the horizontal polarizing film becomes 45°.
[0535] In the optical laminate MC'1, the COP film 1 corresponds to the first phase element, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned phase difference film 6 corresponds to the second phase element.
[0536] <Examples 18 to 32>
[0537] Except for the laminate A, the same members as in Examples 2 to 16 were used, and the production method was similar to that of Example 17, thereby obtaining Examples 18 to 32 including horizontal polarizing films.
[0538] <Comparative Example 1>
[0539] After the coated surface of the vertical polarizing film MC in Example 1 was subjected to corona treatment, the surface of the adhesive sheet 1 from which the diaphragm (MRF38) was peeled off was adhered to produce a laminate G. The laminate G is a PET film (MRV38 (V04)) / HC layer 2 / orientation layer 4 / vertical polarizing film MC / adhesive layer 1 / diaphragm (MRV38 (V04)). The HC-COP film 2 in the laminate C was used as the HC-COP film 1, and its HC surface was subjected to corona treatment. The diaphragm of the laminate G was peeled off to expose the adhesive layer 1, and the exposed adhesive layer 1 was adhered to the HC surface of the laminate C, and the outermost PET film (MRV38 (V04)) was peeled off to obtain Comparative Example 1. The layer structure of this comparative example 1 is HC layer 2 / orientation layer 4 / vertical polarizing film MC / adhesive layer 1 / HC-COP film 1 (HC layer / COP film 1) / water-based adhesive / polarizing film / adhesive layer 1 / orientation layer D / horizontally oriented phase difference film 6 / adhesive layer 9 / vertically oriented phase difference film 7 / orientation layer 8 / COP film ZF. In the laminate of comparative example 1, the orientation layer 4 / vertical polarizing film MC is equivalent to the vertical polarizing film, the COP film 1 constituting the HC-COP film 1 is equivalent to the first phase element, and the orientation layer D / horizontally oriented phase difference film 6 is equivalent to the second phase element. It should be noted that the HC layer constituting the HC-COP film 1 is non-oriented.
[0540] The properties of the phase element, the vertical polarization film, and the polarizing plate used in each of the Examples and Comparative Examples are shown in Table 1-1 and Table 1-2.
[0541] In Table 1-1 and Table 1-2, M of the dichroic dye represents magenta dye, C represents cyan dye, Y represents yellow dye, and θ of the polarizer represents the angle between the slow axis of the first phase element and the absorption axis of the polarizer.
[0542] [Table 1-1]
[0543]
[0544] *1 “COP1” means “COP membrane 1”
[0545] *2 “COP2” means “COP membrane 2”
[0546] *3 “Q” stands for “Orientation layer 9 / retardation film Q1”
[0547] *4 “Z1” means “Orientation layer D / horizontally oriented phase difference film 6”
[0548] *5 “Z1 / Z2” means “alignment layer D / horizontally aligned phase difference film 6 / adhesive layer 9 / vertically aligned phase difference film 7 / alignment layer 8”
[0549] [Table 1-2]
[0550]
[0551] *1 “HC1-COP1” and “COP1” mean “COP membrane 1”
[0552] *2 “COP2” means “COP membrane 2”
[0553] *3 "Q" indicates orientation layer 9 / retardation film Q1"
[0554] *4 “Z1” means orientation layer D / horizontally oriented phase difference film 6”
[0555] *5 “Z1 / Z2” means “alignment layer D / horizontally aligned phase difference film 6 / adhesive layer 9 / vertically aligned phase difference film 7 / alignment layer 8”
[0556] <Evaluation method>
[0557] 1. Uneven white display
[0558] The front glass and polarizing plate of the "Galaxy S5" (organic EL display device) manufactured by SAMSUNG are removed, and the display device is taken out. The COP film ZF of the optical laminate produced by the above method is peeled off and attached to the above-mentioned taken-out display device with the help of an adhesive sheet 1. Then, text is displayed on the screen of the display device, and the presence or absence of unevenness is visually observed through polarized sunglasses from a direction with an elevation angle of 45° relative to the front of the screen. The screen display at this time uses a white display as the background (back) and displays text in black. It should be noted that the observation is to observe in all directions while rotating the display device in the plane.
[0559] A: No unevenness observed (0% of the white display area of the background)
[0560] B: Almost no unevenness is observed (exceeding 0% and 10% or less of the white display area of the background)
[0561] C: Unevenness is slightly observed, but there is no problem in practical use (exceeding 10% and not more than 50% of the white display area of the background)
[0562] D: Unevenness was observed, which was problematic in practical use (exceeding 50% of the white display area of the background)
[0563] Table 2 shows the evaluation results.
[0564] 2. Coloring when displaying black
[0565] The front glass and polarizing plate were removed from the "Galaxy S5" manufactured by SAMSUNG, and the display device was taken out. The COP film ZF of the optical laminate prepared by the above method was peeled off and attached to the above-taken display device via the adhesive sheet 1. Then, the reflection hue was confirmed when the display device was observed from an oblique direction with the naked eye in a state where the power of the display device was turned off (black display), and the evaluation was performed according to the evaluation criteria shown below.
[0566] A: I can’t feel the color tone
[0567] B: Almost no color tone
[0568] C: Slightly feel the color tone
[0569] D: Clearly feel the color tone
[0570] Table 2 shows the evaluation results.
[0571] It should be noted that the reflected color tone evaluated above is the color tone of internal reflected light that is slightly observed due to reflection inside the organic EL display device. This internal reflected light can be observed during black display.
[0572] Furthermore, when the display device was observed from the front with naked eyes in a state where the power supply was turned off, a reflected tint was also confirmed, but no tint was perceived in any of the Examples and Comparative Examples.
[0573] [Table 2-1]
[0574]
[0575] [Table 2-2]
[0576]
[0577] Description of Reference Numerals
[0578] 1: First phase element
[0579] 2: Vertical polarizing film
[0580] 3: Polarizer
[0581] 4: Second phase element
[0582] 5: Another phase element
[0583] 11: Multiple phase difference plates
[0584] 21: Laminated body.
Claims
1. A laminate comprising, in order, a first phase element, a vertical polarizing film, a polarizing plate, and a second phase element, The first phase element is a phase element that exhibits a phase difference within a plane, The angle between the slow axis of the first phase element and the absorption axis of the polarizer is greater than or equal to 35° and less than or equal to 55°, or greater than or equal to 125° and less than or equal to 145°. The vertical polarizing film is a cured product of a composition comprising a polymerizable liquid crystal compound and a dichroic pigment, and satisfies the following formulas (1) and (2): 0.00 1≤AxC≤0.3 (1) AxC(z=60) / AxC>2(2) In formulas (1) and (2), AxC and AxC(z=60) are the absorbance of the vertical polarizing film at the absorption maximum wavelength of 400nm to 750nm. AxC represents the absorbance of linear polarized light vibrating in the x-axis direction, and AxC(z=60) represents the absorbance of linear polarized light vibrating in the x-axis direction when the vertical polarizing film is rotated 60° with the y-axis as the rotation axis. Here, the x-axis refers to an arbitrary direction in the plane of the perpendicular polarizing film, the y-axis refers to a direction perpendicular to the x-axis in the film plane, and the z-axis refers to the thickness direction of the perpendicular polarizing film.
2. The laminate according to claim 1, wherein The absorption maximum wavelength of the vertical polarizing film in the tilted direction is greater than or equal to 500 nm and less than 700 nm, and the first phase element satisfies the following formula (3): Re(450)≤135nm (3) In the formula (3), Re(450) represents the in-plane phase difference value of the first phase element at a wavelength of 450 nm.
3. The laminate according to claim 1, wherein The absorption maximum wavelength of the vertical polarizing film in the tilted direction is greater than or equal to 400 nm and less than 500 nm, and the first phase element satisfies at least one of the following equations (4) and (5): Re(550)≥95nm(4) Re(650)≥95nm(5) In equations (4) and (5), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm.
4. The laminate according to claim 1, wherein The absorption maximum wavelength of the vertical polarizing film in the tilted direction is greater than or equal to 400 nm and less than or equal to 600 nm, and the first phase element satisfies the following formula (6): Re(650)≥≥95nm(6) In the formula (6), Re(650) represents the in-plane phase difference value of the first phase element at a wavelength of 650 nm.
5. The laminate according to claim 1, wherein The maximum absorption wavelength of the vertical polarizing film in the tilted direction is 600 nm to 700 nm, and the first phase element satisfies at least one of the following equations (7) and (8): Re(450)≤135nm(7) Re(550)≤150nm(8) In equations (7) and (8), Re(λ) represents the in-plane phase difference value of the first phase element at a wavelength of λ nm.
6. The laminate according to claim 1 or 2, wherein: The second phase element includes a cured film of a composition containing a polymerizable liquid crystal compound.
7. The laminate according to claim 1 or 2, wherein: The polarizing plate includes a cured film of a composition containing a polymerizable liquid crystal compound and a dichroic dye. An organic EL display device comprising the laminate according to claim 1 or 2.
Citation Information
Patent Citations
JP1972019156U
Compound, optical film, and manufacturing method for optical film
JP2009173893A
Magnetic transfer master substrate, magnetic transfer method using the same and magnetic transfer medium
JP2012033249A
Polarizing film, circularly polarizing plate and their manufacturing method
JP2013101328A
Polymerizable liquid crystal composition and retardation plate
JP2019003177A